Polymer emulsion plugging agent, preparation method and application thereof, and drilling fluid
Patent Information
- Application Number
- CN202610920131.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-30
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明的目的是为了克服现有技术存在的传统封堵剂的封堵效果差、封堵层易脱落,与其他钻井液组分配伍效果较差的问题,提供一种聚合物乳液封堵剂及其制备方法与应用、钻井液,该聚合物乳液封堵剂能够迅速渗透到地层的微孔隙中,在井壁上形成泥饼,致密性好、韧性好,可有效提高封堵效果,能够有效地阻止流体或气体的泄漏,满足层理和微裂缝发育的硬脆性和破碎性地层钻进需求,同时还兼备生产工艺简单易操作和价格低廉等优势
(1)本发明提供的聚合物乳液封堵剂具有良好的封堵能力,封堵剂可进入地层微孔隙、微裂缝,提高封堵层致密性,帮助改善滤饼质量,形成薄而韧性高的滤饼,降低钻井液的高温高压滤失量;
Smart Images

Figure CN123003777A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of drilling fluid technology, specifically to a polymer emulsion plugging agent, its preparation method and application, and drilling fluid. Background Technology
[0002] With the exploration and development of unconventional oil and gas such as shale gas and shale oil, oil-based drilling fluids are being used more and more widely. However, due to the development of micro-nano pores and fractures in shale gas and shale oil reservoirs, oil-based drilling fluids are prone to leakage into the deep formation during drilling. On the one hand, leakage of oil-based drilling fluids increases the cost of drilling fluids, and on the other hand, the fracturing effect of oil may induce wellbore instability.
[0003] During oil drilling, wellbore sealing is necessary to prevent drilling fluid loss or wellbore instability. Sealing agents are key agents for enhancing the sealing properties of drilling fluids. They seal micropores and microfractures in the formation, helping to form a thin, dense filter cake on the wellbore, reducing the intrusion of filtrate and solid phases into the formation, improving the formation's pressure-bearing capacity, decreasing the likelihood of well leakage, and enhancing wellbore stability.
[0004] Currently, the plugging agents used in oil-based drilling fluids are mainly asphalt-based, polymer-based, and inorganic particulate plugging agents. Asphalt-based products have the disadvantages of polluting the environment and reducing drilling speed; polymer-based products have the disadvantages of high cost, difficulty in degradation, and impact on rheological properties (thickening); inorganic particulate plugging agents have poor suspension properties, are rigid and difficult to deform, resulting in poor plugging performance, poor compatibility with base oils, and disadvantages such as uneven dispersion and reduced demulsification voltage.
[0005] In drilling fluid plugging technology, traditional plugging methods suffer from poor plugging effect and easy detachment of the plugging layer. Nanofilm plugging technology, on the other hand, effectively improves the plugging effect by forming a nanoscale protective film on the well wall. However, most inorganic plugging agents prepared by nano-micro technology are rigid plugs with weak sealing. Therefore, plugging agents that can effectively improve the plugging effect are needed. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems of poor sealing effect, easy detachment of the sealing layer, and poor compatibility with other drilling fluid components of existing traditional plugging agents. This invention provides a polymer emulsion plugging agent, its preparation method, and its application in drilling fluid. This polymer emulsion plugging agent can rapidly penetrate into the micropores of the formation, forming a mud cake on the well wall. It has good density and toughness, effectively improving the sealing effect and preventing fluid or gas leakage. It meets the drilling requirements of hard, brittle, and fractured formations with well-developed bedding and microfractures. Furthermore, it has the advantages of simple and easy-to-operate production process and low price.
[0007] To achieve the above objectives, a first aspect of the present invention provides a polymer emulsion plugging agent, wherein the polymer emulsion plugging agent comprises an acrylate polymer; The acrylate polymer comprises the structural unit shown in formula (Ⅰ). Equation (I); In formula (Ⅰ), R is an alkyl group having 2-20 carbon atoms; The acrylate polymer has a weight-average molecular weight of 350,000-450,000 g / mol and a number-average molecular weight of 250,000-350,000 g / mol; the polymer emulsion plugging agent has a median particle size D. 50 The wavelength range is 80-520nm.
[0008] Preferably, the molecular weight distribution of the acrylate polymer is 1.2-1.4, more preferably 1.25-1.33; Preferably, the weight-average molecular weight of the acrylate polymer is 370,000-430,000 g / mol.
[0009] Preferably, the number-average molecular weight of the acrylate polymer is 270,000-330,000 g / mol.
[0010] Preferably, the median particle size D of the polymer emulsion plugging agent is... 50 The wavelength range is 100-300nm, and more preferably 180-200nm.
[0011] Preferably, in formula (Ⅰ), R is an alkyl group having 3-18 carbon atoms.
[0012] Preferably, the acrylate polymer is obtained by emulsion polymerization of acrylate soft monomers.
[0013] Preferably, the acrylate soft monomer is selected from at least one of butyl acrylate, isooctyl acrylate, and octadecyl acrylate.
[0014] A second aspect of the present invention provides a method for preparing a polymer emulsion blocking agent, wherein the method includes the following steps: In the presence of an initiator and under a protective atmosphere, an emulsion polymerization reaction is carried out on an emulsion system containing acrylate soft monomers and emulsifiers. The emulsifier includes ionic emulsifiers and nonionic emulsifiers; The acrylate soft monomer has the structure shown in formula (II). Formula (II); In formula (II), R is an alkyl group having 2-20 carbon atoms; In the emulsifier, the mass ratio of the nonionic emulsifier to the ionic emulsifier is 3-5:1.
[0015] A third aspect of the present invention provides a polymer emulsion blocking agent prepared by the preparation method described in the second aspect.
[0016] The fourth aspect of this invention provides the application of the polymer emulsion plugging agent described in the first or third aspect in the field of drilling fluids.
[0017] A fifth aspect of the present invention provides a drilling fluid, wherein the drilling fluid comprises the polymer emulsion plugging agent described in the first or third aspect.
[0018] The beneficial effects achieved through the above technical solution are as follows: (1) The polymer emulsion plugging agent provided by the present invention has good plugging ability. The plugging agent can enter the formation micropores and microfractures, improve the density of the plugging layer, help improve the filter cake quality, form a thin and tough filter cake, and reduce the high temperature and high pressure filtration loss of drilling fluid. (2) In this invention, preferably, the polymer emulsion plugging agent has good compatibility with both diesel-based drilling fluid and biomass-based drilling fluid. The polymer emulsion plugging agent is used in combination with core-shell structure materials and drilling fluid emulsifiers to formulate drilling fluid. Through the synergistic effect between the various treatment agents, the drilling fluid has good properties in terms of high-temperature rheology, high-temperature and high-pressure filtration loss, formation protection, and biodegradability at 200°C. The raw materials are widely available and inexpensive, which reduces the production cost of the drilling fluid. Attached Figure Description
[0019] Figure 1 This is the infrared spectrum of the polymer emulsion blocking agent prepared in Example 1 of the present invention; Figure 2 This is a particle size distribution diagram of the polymer emulsion plugging agent prepared in Example 1 of the present invention; Figure 3 These are SEM images and EDS elemental distribution maps of Example 1, which shows the preparation of core-shell structured materials. Figure 4 Example 1: SEM image and EDS elemental distribution map of oxygen vacancy-type doped transition metal oxide without a shell. Figure 5 This is a graph of the XPS peak intensity fitting of the product of Example 1, which is a core-shell structure material preparation. Figure 6 This is the pH-titrate volume curve recorded during the hydroxyl value test process of Example 1 for the preparation of polyhydroxy oligomers; Figure 7 The results are infrared spectral analysis results from Example 1 of the preparation of polyhydroxy oligomers. Figure 8 This is a filter cake photograph from Example 1 of drilling fluid application; Figure 9 This is a scanning electron microscope image of the filter cake from Example 1 of drilling fluid application. Detailed Implementation
[0020] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0021] In this invention, the term "structural unit" refers to the smallest repeating unit that forms a polymer.
[0022] In this invention, the functional groups of the acrylate polymer are analyzed by infrared spectroscopy.
[0023] In this invention, the weight-average molecular weight and number-average molecular weight of the acrylate polymer are determined by gel permeation chromatography (GPC) after demulsification, purification, and dissolution of the polymer emulsion blocking agent. A Shimadzu LC20 high-performance liquid chromatography pump and a Shimadzu RID-20 differential refractive index detector were used for the determination. The mobile phase was chromatographically pure THF, and the standard sample was polystyrene (PS, TOSOH, Japan). The mobile phase flow rate was 1.0 mL / min, and the column temperature was 35 °C.
[0024] In this invention, the polymer emulsion blocking agent sample D is measured according to the wet sample operation procedure of a high-performance laser particle size analyzer. 50 (Median particle size), circulating medium is distilled water. The high-performance laser particle size analyzer is the TopSizer laser particle size analyzer.
[0025] In this invention, the number-average molecular weight of the polyhydroxy oligomers and polyamine oligomers is determined by multi-angle laser light scattering.
[0026] In this invention, the hydroxyl values of the polyhydroxy oligomers and polyamine oligomers are determined by automatic potentiometric titration. Due to the large difference in pKa between carboxyl groups and phenolic hydroxyl groups (ΔpKa≈5-8), carboxyl groups preferentially react with strong bases during titration, while phenolic hydroxyl groups only react at higher pH levels. The pH-titer volume curve is recorded by potentiometric titration, and the carboxyl content is calculated using the first jump point (corresponding to carboxyl neutralization), while the second jump point (if present) corresponds to the phenolic hydroxyl content.
[0027] In this invention, the amine value of the polyamine oligomer is determined by hydrochloric acid-base titration. Specifically, 1-2g of sample is weighed into an Erlenmeyer flask, 50mL of neutral ethanol is added, and after dissolution, 5 drops of bromophenol blue indicator solution are added. The solution is titrated with standard hydrochloric acid until it turns yellow. The endpoint is defined as the solution not fading for 10 seconds. The amine value X1 (mg KOH / g) is calculated according to the following formula (1): X1= Formula (1), where c is the concentration of hydrochloric acid standard solution (mol / L), V is the volume of hydrochloric acid standard solution consumed by the sample (mL), and m is the sample mass (g).
[0028] In this invention, the contents of structural unit A, alkylene groups with 1-6 carbon atoms and structural unit B in the polyhydroxy oligomer are calculated by the amount of feed. The contents of structural unit A, alkylene groups with 1-6 carbon atoms and structural unit C in the polyamine oligomer are calculated by the amount of feed.
[0029] In this invention, the average particle size of the core-shell structure material is the distance between the two farthest points of the core particles. When the core is a rod-shaped structure, the average particle size is the length of the long side of the particle. The average particle size of the core-shell structure material is measured using a scanning electron microscope (SEM). For example, the sample is observed using an SEM, the particle size within the field of view is statistically analyzed, and the average value is obtained through simulation measurement using accompanying software. To obtain more accurate results, the particle sizes from multiple fields of view can be statistically averaged. The SEM used is a ZEISS scanning electron microscope manufactured by Carl Zeiss GmbH, Germany.
[0030] In this invention, the composition and content of the core of the core-shell structure material are determined by X-ray photoelectron spectroscopy (XPS), and the testing instrument is the EscaLab250Xi X-ray photoelectron spectrometer manufactured by Thermo Fisher Scientific.
[0031] In this invention, the average thickness of the shell layer of the core-shell structure material is determined by transmission electron microscopy (TEM). TEM allows observation of the different color intensities between the core and shell. Specifically, the thickness of the shell layer is measured at 50 randomly selected locations within the TEM image field, and the average value is calculated. The TEM used is a JEOL-2010 field emission high-resolution transmission electron microscope manufactured by Nippon Electron Ltd.
[0032] In this invention, the content of different structural units in the shell layer of the core-shell structure material is determined by the feeding ratio.
[0033] In this invention, the shell coverage rate of the core-shell structure material refers to the ratio of the area of the shell covering the surface of the core to the total area of the core. The coverage rate is detected by multi-region scanning using a transmission electron microscope (TEM). Specifically, 20 core-shell structure material particles are randomly selected from the TEM field of view, and their surface shell coverage is observed. The shell coverage rate is then analyzed and calculated using the accompanying software.
[0034] In this invention, microbeam analysis and energy dispersive spectroscopy (EDS) can be used to further test the shell coating of core-shell structured materials. For example, EDS can be used to observe the elemental composition of the core-shell structured materials, scan to determine the surface metal elements, and prove that the shell layer has a good coating effect on the core. The EDS spectrometer used is the EDS spectrometer attached to a ZEISS scanning electron microscope manufactured by Carl Zeiss GmbH, Germany.
[0035] In this invention, the core-shell structure material is heated and calcined until the mass change stabilizes at 600°C. The remaining mass and the lost mass after calcination are compared to calculate the mass ratio of the core and the shell.
[0036] In this invention, the peak intensity of the core-shell structure material is measured by XPS, and the proportion of the vacancy oxygen peak area to the total peak area is calculated by software fitting curves, which reflects the oxygen vacancy situation in the core.
[0037] In this invention, the performance of the drilling fluid is tested in accordance with the People's Republic of China National Standard GB / T 16783.2-2012 "Field Testing of Drilling Fluids for Petroleum and Natural Gas Industry - Part 2: Oil-based Drilling Fluids".
[0038] In this invention, the terms "first", "second", "third" and "fourth" are merely used to distinguish different raw materials or operation steps, and do not limit the order of reaction or addition of raw materials.
[0039] The first aspect of the present invention provides a polymer emulsion plugging agent, wherein the polymer emulsion plugging agent comprises an acrylate polymer; The acrylate polymer comprises the structural unit shown in formula (Ⅰ). Equation (I); In formula (Ⅰ), R is an alkyl group having 2-20 carbon atoms; The acrylate polymer has a weight-average molecular weight of 350,000-450,000 g / mol and a number-average molecular weight of 250,000-350,000 g / mol; the polymer emulsion plugging agent has a median particle size D. 50 The wavelength range is 80-520nm.
[0040] In this invention, the polymer emulsion plugging agent particles can rapidly penetrate into the micropores of the formation and form a nanoscale protective film on the well wall, which can effectively improve the plugging effect and effectively prevent the leakage of fluids or gases. It meets the drilling requirements of hard, brittle, and fractured formations with bedding and microfracture development, and also has the advantages of simple and easy production process and low price.
[0041] During the sealing process, polymer emulsion particles can rapidly penetrate into the formation or pores, forming a dense sealing film. This film possesses excellent flexibility and strength, effectively preventing fluid or gas leakage. By precisely controlling the size and shape of the emulsion polymer particles, the distribution and penetration behavior of the sealing agent in the formation can be precisely controlled. This not only improves sealing efficiency and achieves pre-sealing to prevent leakage and collapse, but also reduces damage to the surrounding formation.
[0042] According to a preferred embodiment of the present invention, the weight-average molecular weight of the acrylate polymer is 350,000-450,000 g / mol, for example, 350,000 g / mol, 360,000 g / mol, 370,000 g / mol, 380,000 g / mol, 390,000 g / mol, 400,000 g / mol, 410,000 g / mol, 420,000 g / mol, 430,000 g / mol, 440,000 g / mol, 450,000 g / mol, or any range between the two, preferably 370,000-430,000 g / mol.
[0043] According to a preferred embodiment of the present invention, the number average molecular weight of the acrylate polymer is 250,000-350,000 g / mol, for example, 250,000 g / mol, 260,000 g / mol, 270,000 g / mol, 280,000 g / mol, 290,000 g / mol, 300,000 g / mol, 310,000 g / mol, 320,000 g / mol, 330,000 g / mol, 340,000 g / mol, 350,000 g / mol, or any range between the two, preferably 270,000-330,000 g / mol.
[0044] According to a preferred embodiment of the present invention, the molecular weight distribution of the acrylate polymer is 1.2-1.4, for example 1.2, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, 1.3, 1.31, 1.32, 1.33, 1.34, 1.35, 1.36, 1.37, 1.38, 1.39, 1.4, or any range between the two, preferably 1.25-1.33. In this invention, the acrylate polymer has a narrow molecular weight distribution, good polymer stability, and good film-forming quality.
[0045] According to a preferred embodiment of the present invention, the median particle size D of the polymer emulsion plugging agent is... 50The particle size is 80-520 nm, preferably 100-300 nm, such as 100 nm, 120 nm, 140 nm, 150 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, 400 nm, 500 nm, 520 nm, or any range between the two, more preferably 180-200 nm. In this invention, the median particle size of the polymer emulsion blocking agent is in the nanometer range, and the polymer emulsion blocking agent has good stability and does not separate after long-term storage.
[0046] According to a preferred embodiment of the present invention, the solid content of the polymer emulsion plugging agent is 15-25 wt%, preferably 19-21 wt%. In this invention, the solid content in the polymer emulsion plugging agent is obtained by drying at 105°C for 4 hours and comparing the mass of the dried sample with the mass of the original sample.
[0047] The polymer emulsion plugging agent provided by this invention has good plugging ability. The nanoparticles can enter the formation micropores and microfractures, improve the density of the plugging layer, help improve the filter cake quality, form a thin and dense filter cake, reduce the filtration loss at high temperature and high pressure, and the polymer emulsion plugging agent has good compatibility with both diesel-based drilling fluid and biomass-based drilling fluid.
[0048] According to a preferred embodiment of the present invention, the acrylate polymer is obtained by emulsion polymerization of acrylate soft monomers. The acrylate soft monomers have the conventional meaning in the art, referring to vinyl monomers whose homopolymer glass transition temperature is significantly lower than room temperature; any acrylate soft monomer well-known to those skilled in the art is acceptable.
[0049] According to a preferred embodiment of the present invention, in formula (I), R is an alkyl group having 3-18 carbon atoms. The alkyl group is a straight-chain alkyl group or a branched-chain alkyl group. Preferably, R is propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecanyl, or octadecyl.
[0050] According to a preferred embodiment of the present invention, the acrylate soft monomer is selected from at least one of butyl acrylate, isooctyl acrylate and octadecyl acrylate.
[0051] According to a preferred embodiment of the present invention, the polymer emulsion plugging agent further contains an emulsifier.
[0052] According to a preferred embodiment of the present invention, in the polymer emulsion plugging agent, the mass ratio of the acrylate polymer to the emulsifier is (170-180):(11-13), preferably (170-180):(11.5-12.8).
[0053] According to a preferred embodiment of the present invention, the emulsifier comprises an ionic emulsifier and a nonionic emulsifier. The present invention uses a combination of ionic and nonionic emulsifiers, with the two types of emulsifier molecules alternately adsorbed onto the surface of the latex particles. This reduces the electrostatic repulsion between ions on the same particle, enhances the adsorption strength of the emulsifier on the particle, reduces the charge density on the latex particle surface, and makes it easier for negatively charged free radicals to enter the latex particles, thereby increasing the emulsion polymerization rate and obtaining nanoscale particles.
[0054] According to a preferred embodiment of the present invention, the mass ratio of the nonionic emulsifier to the ionic emulsifier in the emulsifier is 3-5:1, for example 3:1, 3.2:1, 3.4:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 4.8:1, 5:1, or any range between the two, preferably 3.2-4:1. In this invention, the nonionic and ionic emulsifiers are described in detail in the subsequent description and will not be repeated here.
[0055] This invention uses acrylate soft monomers as polymerizing monomers to form acrylate polymers as plugging agents. First, esters have good oil solubility, which can improve the lipophilicity of the plugging agent. Acrylate polymer plugging agents usually have good deformation ability and film-forming properties, making it easier to enter nano- and micro-sized pores and cracks to form effective plugs. Second, esters themselves can act as emulsifiers, increasing the demulsification voltage of drilling fluid and enhancing the stability of the system, thus achieving the dual functions of enhanced plugging and emulsification. Furthermore, acrylate polymers have a certain degree of viscosity, which can act as a binder to the micropores and micro-fractures of the formation, enhancing the firmness of the plug.
[0056] According to a preferred embodiment of the present invention, the polymer emulsion plugging agent further contains a solvent.
[0057] According to a preferred embodiment of the present invention, the content of the acrylate polymer in the polymer emulsion plugging agent is 15-25 wt%.
[0058] A second aspect of the present invention provides a method for preparing a polymer emulsion blocking agent, wherein the method includes the following steps: In the presence of an initiator and under a protective atmosphere, an emulsion system containing acrylate soft monomers and emulsifiers undergoes a polymerization reaction. The emulsifier includes ionic emulsifiers and nonionic emulsifiers; The acrylate soft monomer has the structure shown in formula (II). Formula (II); In formula (II), R is an alkyl group having 2-20 carbon atoms; In the emulsifier, the mass ratio of the nonionic emulsifier to the ionic emulsifier is 3-5:1.
[0059] The preparation method provided by this invention has mild reaction conditions, simple production process, low overall cost, and high product cost performance. The obtained polymer emulsion plugging agent exhibits good plugging performance, helps improve mud cake quality, and forms a thinner, tougher, and denser mud cake, which can reduce the high temperature and high pressure filtration loss of drilling fluid.
[0060] According to a preferred embodiment of the present invention, in the emulsion system, the mass percentage of acrylate monomers in the monomers undergoing emulsion polymerization is not less than 60 wt%, preferably not less than 90 wt%.
[0061] According to a preferred embodiment of the present invention, in formula (II), R is an alkyl group having 3-18 carbon atoms. The source of the acrylate soft monomer is not particularly limited; it can be commercially available or prepared using existing methods, and any commercially available monomer is acceptable. The acrylate monomer is as described above and will not be repeated here.
[0062] According to a preferred embodiment of the present invention, the mass ratio of the acrylate soft monomer to the emulsifier is (170-180):(11-13), preferably (170-180):(11.5-12.8). In some embodiments provided by the present invention, the mass ratio of the acrylate soft monomer to the emulsifier is specifically 175:11.7, 170:11, or 180:12.8.
[0063] According to a preferred embodiment of the present invention, the emulsion system further comprises water as a solvent. The mass ratio of the acrylate soft monomer to the solvent is preferably (170-180):(700-750); in some embodiments provided by the present invention, the mass ratio of the acrylate soft monomer to water is specifically 175:730, 170:750, or 180:700.
[0064] According to a preferred embodiment of the present invention, the preparation method of the emulsion system includes: mixing and emulsifying an acrylate soft monomer, an emulsifier and a solvent, wherein the mixing and emulsification time is 15-25 min, more preferably 20-25 min.
[0065] According to a preferred embodiment of the present invention, the pH value of the emulsified system is 8-9.
[0066] In this invention, since most latexes are very sensitive to hydrogen ion concentration, a certain amount of pH adjuster is usually added to stabilize the latex and adjust the pH. Preferably, a pH adjuster is also added during the mixing and emulsification process.
[0067] According to a preferred embodiment of the present invention, the type and amount of pH adjuster are not particularly limited, as long as the pH value of the emulsion volume is 8-9, and the pH adjuster is well known to those skilled in the art. Sodium bicarbonate and / or potassium bicarbonate are preferred in this invention.
[0068] In one specific embodiment of the present invention, the mass ratio of the acrylate soft monomer to the pH adjuster is (170-180):(1.8-2.0), specifically 175:1.9, 170:1.8 or 180:2.0.
[0069] According to a preferred embodiment of the present invention, the protective atmosphere can be any protective atmosphere known to those skilled in the art, and there are no special limitations, such as at least one of nitrogen, helium and argon, with nitrogen being preferred in the present invention.
[0070] According to the present invention, the emulsifier used in the emulsion polymerization includes ionic emulsifiers and nonionic emulsifiers. The present invention uses ionic emulsifiers and nonionic emulsifiers in combination. The molecules of the two emulsifiers are alternately adsorbed on the surface of latex particles, which can reduce the electrostatic repulsion between ions on the same particle, enhance the adsorption strength of the emulsifier on the particle, reduce the charge density on the surface of the latex particle, and make it easier for negatively charged free radicals to enter the latex particle, thereby increasing the emulsion polymerization rate. The HLB value of the ionic emulsifier is preferably 30-40, more preferably 35-40, and even more preferably 38-40. The HLB value of the nonionic emulsifier is preferably 10-20, more preferably 12-18, even more preferably 14-15, and most preferably 14.5. Increasing the ratio of nonionic / ionic emulsifiers will increase the particle size of the emulsion and thus the particle size of the product. However, ionic emulsifiers are prone to foaming, causing foaming of the reaction solution, and even causing foaming of the drilling fluid when added to it.
[0071] According to a preferred embodiment of the present invention, the mass ratio of the nonionic emulsifier to the ionic emulsifier is 3-5:1, for example 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 4.8:1, 5:1, or any range between the two, preferably 3.2-4:1. In a specific embodiment provided by the present invention, the mass ratio of the nonionic emulsifier to the ionic emulsifier is 3.5:1, which results in a latex that is less prone to foaming, better latex stability, and a median particle size of the polymer emulsion blocking agent that is conducive to maintaining between 100-300 nm. If the mass ratio of the nonionic emulsifier to the ionic emulsifier is too high, the resulting product particle size will be too large; if the mass ratio is too low, the resulting product particle size will be too small, resulting in severe foaming, making industrial production impossible, and the product is prone to overflowing from the reactor.
[0072] According to a preferred embodiment of the present invention, the nonionic emulsifier is an alkylphenol polyoxyethylene ether, preferably selected from at least one of dodecylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, and octylphenol polyoxyethylene ether.
[0073] According to a preferred embodiment of the present invention, the weight-average molecular weight of the alkylphenol polyoxyethylene ether has a wide selectable range, and according to the variation of its ethylene oxide addition number (EO number), the preferred weight-average molecular weight is 400-1500 g / mol.
[0074] According to a preferred embodiment of the present invention, the ionic emulsifier is an alkyl sulfate, wherein the alkyl group in the alkyl sulfate preferably has 10-16 carbon atoms, more preferably 12-14. The alkyl sulfate is preferably selected from at least one of dodecyl sulfate, tridecyl sulfate, and tetradecyl sulfate, more preferably sodium dodecyl sulfate and / or ammonium dodecyl sulfate.
[0075] In one specific embodiment of the present invention, the alkylphenol polyoxyethylene ether is preferably dodecylphenol polyoxyethylene ether, which has good emulsifying and wetting properties; the alkyl sulfate is preferably dodecyl sulfate, which has excellent emulsifying and foaming capabilities.
[0076] According to a preferred embodiment of the present invention, the mass ratio of the acrylate soft monomer to the initiator is (170-180):(1.3-1.5). In a specific embodiment provided by the present invention, the mass ratio of the acrylate soft monomer to the initiator is specifically 175:1.4, 170:1.3, or 180:1.5.
[0077] According to a preferred embodiment of the present invention, the initiator is added in the form of an initiator solution, preferably water as the solvent.
[0078] According to a preferred embodiment of the present invention, the mass concentration of the initiator in the initiator solution is 3-5%, for example 3%, 3.5%, 4%, 4.5%, 5%, or any range between the two.
[0079] According to a preferred embodiment of the present invention, the initiator is a persulfate, preferably potassium persulfate and / or ammonium persulfate.
[0080] According to a preferred embodiment of the present invention, the initiator is added at a time of 15-30 minutes, preferably 20-30 minutes. In this invention, after mixing and emulsifying, it is preferable to heat to the temperature of the emulsion polymerization reaction before adding the initiator solution; the initiator solution is preferably added dropwise, more preferably through a constant-pressure dropping funnel; specifically, the initiator solution is preferably added dropwise within 20-30 minutes, more preferably within 25 minutes. In this invention, adding the initiator in the above manner helps to control the molecular weight distribution of the emulsion polymerization product to be more concentrated. Adding the initiator too quickly will cause the polymerization reaction to proceed violently, resulting in an excessively broad molecular weight distribution of the acrylate polymer obtained from the reaction.
[0081] According to a preferred embodiment of the present invention, the emulsion polymerization reaction conditions can be selected over a wide range. The emulsion polymerization reaction conditions include: a polymerization temperature of 60-90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or any range between the two, preferably 70-80°C; and a polymerization time of 1-4 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 4 hours, or any range between the two, preferably 1.5-2.5 hours.
[0082] In this invention, the residual status of acrylate soft monomers in the raw materials can be determined by gas chromatography to confirm the progress of the emulsion polymerization reaction. If no acrylate soft monomers remain, the reaction is complete.
[0083] In this invention, preferably, the polymer emulsion plugging agent is obtained by cooling to room temperature after the polymerization reaction, which can be directly used to prepare drilling fluid without the need for additional separation, and the operation is simple.
[0084] The third aspect of this invention provides a polymer emulsion blocking agent prepared by the preparation method described in the second aspect.
[0085] The fourth aspect of this invention provides the application of the polymer emulsion plugging agent described in the first or third aspect in the field of drilling fluids.
[0086] The polymer emulsion plugging agent provided by this invention has good plugging ability. The nanoparticles can enter the formation micropores and microfractures, improve the density of the plugging layer, help improve the filter cake quality, form a thin and dense filter cake, reduce the filtration loss at high temperature and high pressure, and the polymer emulsion plugging agent has good compatibility with both diesel-based drilling fluid and biomass-based drilling fluid.
[0087] A fifth aspect of the present invention provides a drilling fluid, wherein the drilling fluid comprises the polymer emulsion plugging agent described in the first or third aspect.
[0088] The polymer emulsion plugging agent particles provided by this invention can quickly penetrate into the micropores of the formation to form a dense plugging film. This film has good flexibility and strength and can effectively prevent the leakage of fluids or gases, meeting the drilling requirements of hard, brittle, and fractured formations with bedding and microfracture development.
[0089] According to a preferred embodiment of the present invention, the base fluid is an oil-based base fluid and / or a biomass-based base fluid. In this invention, the polymer emulsion plugging agent exhibits good compatibility with both oil-based and bio-based drilling fluids. There are no particular limitations on the types of components in the drilling fluid, such as filtration reducers, emulsifiers, and organic clays. Conventional filtration reducers, emulsifiers, organic clays, and density modifiers used in drilling fluids can all be formulated in conjunction with the polymer emulsion plugging agent of this invention to prepare drilling fluids.
[0090] According to the present invention, the base liquid comprises diesel oil and an aqueous solution of calcium chloride, or comprises biomass synthesis base liquid and an aqueous solution of calcium chloride. The mass concentration of the aqueous solution of calcium chloride is preferably 25%-35%, more preferably 28%-32%, and even more preferably 30%.
[0091] According to a preferred embodiment of the present invention, the volume ratio of diesel oil to calcium chloride aqueous solution is preferably (80-90):(20-10), more preferably (84-86):(16-14), and even more preferably 85:15; the volume ratio of biomass synthesis base liquid to calcium chloride aqueous solution is preferably (80-90):(20-10), more preferably (84-86):(16-14), and even more preferably 85:15.
[0092] According to a preferred embodiment of the present invention, the content of the polymer emulsion plugging agent in the drilling fluid is 0.5-3g, for example, 0.5g, 1g, 1.5g, 2g, 2.5g, 3g, or any two of the above values, preferably 1-2g, based on a volume of 100mL of the base fluid.
[0093] In one specific embodiment of the present invention, the diesel fuel can be any diesel fuel known to those skilled in the art, and there are no special restrictions. In the present invention, 0# diesel fuel is preferred.
[0094] In a specific embodiment of the present invention, the biomass synthesis base liquid can be any biomass synthesis base liquid known to those skilled in the art, and there are no special limitations. In the present invention, it preferably includes 60-71 parts by weight of mixed plant alkanes and 29-40 parts by weight of mixed fatty alcohol ethers; the mixed plant alkanes include one or more of the compounds with the structure shown in Formula VI; the mixed fatty alcohol ethers include one or more of the compounds with the structure shown in Formula VII.
[0095] C n H 2n+2Formula VI; C m H 2m+2 -OR 4 Formula VII; Where n is an integer between 10 and 15; m is 10, 12, or 14; R 4 It is a C4-C8 alkyl group.
[0096] In a specific embodiment of the present invention, the biomass synthesis base liquid is preferably prepared by the following method: under the action of a catalyst, a natural fatty alcohol pre-fraction, an alkyl reagent and a basic compound are reacted to obtain the biomass synthesis base liquid; specifically, it can be prepared according to Chinese Patent Application No. 201810743989.3.
[0097] In a specific embodiment of the present invention, the drilling fluid preferably further includes a gelling material; the gelling material can be any gelling material known to those skilled in the art, and there are no special limitations. In the present invention, organobentonite is preferred; based on the volume of the base fluid, the content of the gelling material in the drilling fluid is preferably 2-5 g / 100 mL, more preferably 2.5-3.5 g / 100 mL, and even more preferably 3 g / 100 mL.
[0098] According to a preferred embodiment of the present invention, the drilling fluid further comprises a filtration loss reducer. The filtration loss reducer may be any filtration loss reducer well known to those skilled in the art, and there are no particular limitations. The filtration loss reducer is selected from at least one of core-shell structural materials, oxidized bitumen, and humic acid modifiers.
[0099] According to a preferred embodiment of the present invention, the content of the filtration loss reducer in the drilling fluid is 3-5g, preferably 3.5-4.5g, and even more preferably 4g, based on a base fluid volume of 100mL.
[0100] In this invention, the humic acid modified product is preferably a humic acid filtration reducer, more preferably a humic acid amide; specifically, the humic acid filtration reducer is preferably prepared by the following method: humic acid, sodium hydroxide, water, formaldehyde and polyamine are subjected to a first reaction to obtain amination humic acid; the amination humic acid and epoxy fatty acid methyl ester are subjected to a second reaction to obtain the humic acid filtration reducer.
[0101] In one specific embodiment of the present invention, the humic acid filtration loss reducer is prepared according to Example 1 of Chinese Patent Application No. 202110591326.6.
[0102] According to a preferred embodiment of the present invention, the core-shell structure material comprises a core and a shell covering the surface of the core; the core comprises an oxygen vacancy type metal oxide and / or an oxygen vacancy type doped transition metal oxide, and the shell is a polymer layer.
[0103] According to a preferred embodiment of the present invention, XPS characterization shows that the area of the vacancy oxygen peak in the core of the core-shell structure material accounts for no less than 18% of the total peak area.
[0104] In this invention, the core-shell structure material has an inorganic core and a polymer shell layer grown in situ on the surface of the core. The core of the core-shell structure material can effectively improve the temperature resistance of the material, and the polymer in the shell layer does not decompose at high temperatures of 180℃-220℃. When the core-shell structure material is used as a filtration loss reducer, it can still maintain a low viscosity in drilling fluids with high density, and has a good filtration loss reduction effect.
[0105] In this invention, the oxygen vacancy has the conventional definition in the art, referring to a point defect formed in the metal oxide lattice due to the absence of oxygen atoms. In this invention, the oxygen-vacancy type metal oxide and / or oxygen-vacancy type doped transition metal oxide refers to a metal oxide containing oxygen vacancies and / or a doped transition metal oxide containing oxygen vacancies. The oxygen vacancy content is characterized by XPS; a metal oxide with a hole-oxygen peak area accounting for at least 18% of the total peak area is considered to conform to the oxygen-vacancy type metal oxide and / or oxygen-vacancy type doped transition metal oxide of this invention.
[0106] According to a preferred embodiment of the present invention, XPS characterization shows that the area of the vacancy oxygen peak in the core of the core-shell structure material accounts for no less than 18% of the total peak area, for example, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40%, 42%, 44%, 45%, 46%, 48%, 50%, or any range between the two, preferably 24%-50%, more preferably 30%-50%.
[0107] In this invention, XPS testing is performed on core-shell structured materials to measure the integral intensity of the characteristic photoelectron peak of oxygen on the sample surface. The proportion of the hole-oxygen peak area to the total peak area (the total peak area is the sum of the peak areas of different oxygen species in the narrow spectrum scan of oxygen) is calculated by software fitting curves, reflecting the oxygen-containing vacancy situation in the core.
[0108] In this invention, oxygen vacancy-type metal oxides and / or oxygen vacancy-type doped transition metal oxides are used as the core. Their surfaces are rich in oxygen vacancies formed due to crystal isomerism, which can adsorb surrounding active hydroxyl radicals. This causes the polymer to tend to start chain growth directly on the hydroxyl groups on the surface of the metal oxide. The higher the proportion of the hole oxygen peak area to the total peak area, the more oxygen vacancies there are in the metal oxide, the more sites the shell can grow, and the more uniform the shell obtained by in-situ chain growth, resulting in a better coating effect.
[0109] In this invention, the test results of oxygen-containing vacancies before and after the growth of the shell layer on the core surface are basically the same.
[0110] According to a preferred embodiment of the present invention, the mass ratio of the shell to the core is 1:1-10, preferably 1:2-5. In this invention, the core-shell structure material is a polymer as the shell layer. The shell layer has a low molecular weight and has the dual function of sealing and reducing filtration loss. At the same time, it does not contain any gum components and does not increase viscosity during use, which is beneficial to maintaining the rheological properties of the drilling fluid. This solves the problem of difficult rheological control and high viscosity of drilling fluid caused by the high gum content of traditional asphalt-based filtration loss reducers.
[0111] According to a preferred embodiment of the present invention, the shell layer has a coverage rate of 60-100%, preferably 80-100%. In the present invention, the shell layer of the core-shell structure material is grown in situ on the surface of the core, without the need for an initiator. The resulting shell layer has a uniform thickness, a high coverage rate of the core, and good effect. At the same time, the core-shell structure material has good dispersibility and is not prone to agglomeration. The particles can fully react with each other to form a dense filtration reduction layer on the well wall.
[0112] According to a preferred embodiment of the present invention, the shape of the core is not particularly limited and may be selected from at least one of spherical, near-spherical, needle-shaped and rod-shaped, preferably rod-shaped.
[0113] According to a preferred embodiment of the present invention, the average particle size of the core is 50-2000 nm, preferably 50-500 nm.
[0114] According to a preferred embodiment of the present invention, the oxygen vacancy type metal oxide is a lanthanide rare earth metal oxide and / or a transition metal oxide, preferably selected from at least one of cerium oxide, lanthanum oxide, ferric oxide, vanadium pentoxide and manganese dioxide, and more preferably cerium oxide and / or lanthanum oxide.
[0115] According to a preferred embodiment of the present invention, the core surface has a metal element content of 30-70 wt%, preferably 40-58 wt%, an oxygen element content of 30-60 wt%, preferably 40-55 wt%, and a carbon element content of 0-10 wt%, preferably 1-5 wt%.
[0116] In this invention, preferably, the core surface of the core-shell structure material is mainly composed of metal elements and oxygen elements, with very little carbon elements, while the surface of the core-shell structure material product is mainly composed of carbon elements and oxygen elements, with very little metal elements, indicating that the shell layer has a good coating effect on the core.
[0117] According to a preferred embodiment of the present invention, the oxygen vacancy-type doped transition metal oxide comprises a transition metal oxide and a doped metal oxide.
[0118] According to a preferred embodiment of the present invention, the molar ratio of the dopant metal to the transition metal in the oxygen vacancy-type doped transition metal oxide is 1:0.5-6, for example 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, or any range between the two, preferably 1:1-5.
[0119] According to a preferred embodiment of the present invention, the transition metal is selected from at least one of Fe, Co and Ni.
[0120] According to a preferred embodiment of the present invention, the doped metal is selected from at least one of Ca, Mg, K, Ce and La.
[0121] According to a preferred embodiment of the present invention, the average thickness of the shell layer is 2-28 nm, for example 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, or any range between the two, preferably 8-22 nm.
[0122] According to a preferred embodiment of the present invention, the surface of the core-shell structure material has a metal element content of 0-8 wt%, preferably 0-3 wt%, an O element content of 20-60 wt%, preferably 25-50 wt%, and a C element content of 40-80 wt%, preferably 50-70 wt%.
[0123] According to a preferred embodiment of the present invention, when the core is an oxygen-vacancy type metal oxide, the polymerizable monomers of the shell layer comprise soft monomers and hard monomers, wherein the soft monomers are butyl acrylate and / or methyl acrylate, and the hard monomers are selected from at least one of pyrrole, styrene, and aniline. In this invention, the content of the soft and hard monomers is not particularly limited, and they are added according to the polymerization reaction ratios conventional in the art.
[0124] According to a preferred embodiment of the present invention, when the core is an oxygen vacancy-doped transition metal oxide, the polymer monomers of the shell are polycarboxylic acids and polyols.
[0125] According to a preferred embodiment of the present invention, the polyol is selected from at least one of trimethylolpropane, isopentetrol, 1,4-butanediol and 2-propanediol.
[0126] According to a preferred embodiment of the present invention, the polycarboxylic acid is selected from at least one of citric acid, oxalic acid and tartaric acid.
[0127] According to a preferred embodiment of the present invention, when the polymer monomer of the shell layer comprises polycarboxylic acid and polyol, the content of structural units from polyol in the shell layer is 30-70 wt%, preferably 40-60 wt%, and the content of structural units from polycarboxylic acid is 30-70 wt%, preferably 40-60 wt%.
[0128] According to a preferred embodiment of the present invention, the method for preparing the core-shell structure material includes the following steps: The core is brought into contact with the polymer monomer, and the polymer monomer undergoes in-situ chain growth on the core. The core comprises oxygen-vacancy type metal oxides and / or oxygen-vacancy type doped transition metal oxides. XPS characterization showed that the area of the vacancy oxygen peak in the core of the core-shell structured material was not less than 18% of the total peak area.
[0129] In this invention, the core-shell structure material is obtained by in-situ chain growth reaction on the surface of the core to form a polymer shell. Compared with conventional encapsulation-formed core-shell structures, the in-situ growth reaction of this invention does not require the addition of an initiator, and the resulting core-shell structure has good dispersibility and is not prone to aggregation. When applied to drilling fluids, it exhibits excellent high-temperature resistance and does not decompose in environments of 180-200℃. In this invention, the source of the core is not particularly limited; it can be commercially available or prepared using existing methods.
[0130] The core-shell structured material of this invention is used as a filtration loss reducer in drilling fluid. When combined with other drilling fluid components, the core-shell structured material is uniformly dispersed in the drilling fluid. It has a lower viscosity at high density. Through synergistic effect, the drilling fluid exhibits excellent properties in terms of high-temperature rheology, high-temperature and high-pressure filtration loss, formation protection, and biodegradability at 200°C. The raw materials are widely available and inexpensive, which reduces the production cost of drilling fluid.
[0131] According to a preferred embodiment of the present invention, XPS characterization shows that the vacancy oxygen peak area of the core of the core-shell structure material accounts for 24%-50% of the total peak area, preferably 30%-50%.
[0132] According to a preferred embodiment of the present invention, the oxygen vacancy type metal oxide is a lanthanide rare earth metal oxide and / or a transition metal oxide, preferably selected from at least one of cerium oxide, lanthanum oxide, ferric oxide, vanadium pentoxide and manganese dioxide.
[0133] According to a preferred embodiment of the present invention, the oxygen vacancy-type doped transition metal oxide comprises a transition metal oxide and a doped metal oxide.
[0134] According to a preferred embodiment of the present invention, the method for preparing the oxygen vacancy-type doped transition metal oxide includes: contacting a transition metal source and a doped metal source with an excess polycarboxylic acid solution to carry out a precipitation reaction, performing solid-liquid separation on the reaction product, and calcining the obtained solid product to obtain the oxygen vacancy-type doped transition metal oxide.
[0135] According to a preferred embodiment of the present invention, the doped metal source is selected from at least one of Ca source, Mg source, K source, Ce source and La source.
[0136] According to a preferred embodiment of the present invention, the transition metal source is selected from at least one of Fe, Co, and Ni sources. Preferably, the doping metal source and the transition metal source are each independently selected from at least one of nitrates, sulfates, and chlorides. For example, the Ce source is selected from at least one of cerium chloride, cerium nitrate, and cerium sulfate. The La source is selected from lanthanum nitrate and / or lanthanum chloride. The Ca source is calcium chloride and / or calcium nitrate. The Mg source is selected from at least one of magnesium nitrate, magnesium chloride, and magnesium sulfate. The K source is selected from at least one of potassium chloride, potassium nitrate, and potassium sulfate.
[0137] According to a preferred embodiment of the present invention, the Fe source is selected from at least one of ferric nitrate, ferric chloride, and ferric sulfate. The Co source is selected from at least one of cobalt nitrate, cobalt sulfate, and cobalt chloride. The Ni source is selected from at least one of nickel nitrate, nickel sulfate, and nickel chloride.
[0138] According to a preferred embodiment of the present invention, in the oxygen vacancy-type doped transition metal oxide, the molar ratio of the doped metal source to the transition metal source is 1:1-6, preferably 1:2-5, based on metal elements.
[0139] According to a preferred embodiment of the present invention, the conditions for the precipitation reaction include: a reaction time of 10-30 min, preferably 15-20 min; and a reaction temperature of 0-8°C, preferably 0-5°C. Preferably, the precipitation reaction is carried out under stirring conditions.
[0140] In this invention, the method of solid-liquid separation is not particularly limited, but filtration is preferred for solid-liquid separation of the coprecipitated product, followed by washing and drying of the obtained solid product. Washing and drying can be performed according to conventional methods in the art.
[0141] According to a preferred embodiment of the present invention, the calcination conditions include: a calcination temperature of 400-600℃, preferably 450-550℃; and a calcination time of 2-8h, preferably 2-4h.
[0142] According to a preferred embodiment of the present invention, the amount of the polymer monomer used is such that the average thickness of the shell layer is 2-28 nm, preferably 8-22 nm.
[0143] According to a preferred embodiment of the present invention, when the core is an oxygen vacancy type metal oxide, the polymer monomer of the shell layer comprises a soft monomer and a hard monomer, wherein the soft monomer is butyl acrylate and / or methyl acrylate, and the hard monomer is selected from at least one of pyrrole, styrene and aniline.
[0144] According to a preferred embodiment of the present invention, when the core is an oxygen-vacancy-doped transition metal oxide, the polymer monomers of the shell are polycarboxylic acids and polyols. In this invention, the core-shell structure material prepared using the above-mentioned polymer monomers does not decompose at high temperatures of 180-220°C.
[0145] According to a preferred embodiment of the present invention, the conditions for the in-situ chain growth reaction include: a reaction temperature of 15-90°C, preferably 25-60°C; and a reaction pressure of 0.5-0.7 MPa, preferably 0.55-0.65 MPa. The reaction time of the in-situ chain growth reaction is not particularly limited; once the formed shell completely covers the oxygen-vacancy type metal oxide core, the core can no longer initiate a condensation reaction, and the reaction stops. Preferably, the reaction time is 0.5-5 hours, more preferably 1-4 hours.
[0146] According to a preferred embodiment of the present invention, the in-situ chain growth reaction is carried out in the absence of an initiator. In this invention, the core surface has oxygen vacancies, providing sites for the growth of the shell layer on the core surface. This allows for the direct initiation of the in-situ chain growth reaction without the addition of an initiator, resulting in a core-shell structure with good coating effect.
[0147] In this invention, preferably, the solvent for the polycarboxylic acid solution is water.
[0148] According to a preferred embodiment of the present invention, the polycarboxylic acid is added in excess in step (I), which not only facilitates the precipitation reaction, but also reacts with the polyol in step (II) according to the above mass ratio to form a shell. The liquid product of step (I) can be reused.
[0149] In this invention, the range of types of polycarboxylic acids and polyols is quite wide, as described in the foregoing specification, and will not be repeated here.
[0150] In this invention, preferably, the mass ratio of the polycarboxylic acid and the polyol is 1:1-2, more preferably 1:1-1.5.
[0151] In this invention, preferably, the condensation reaction is carried out under the above conditions, with the core as the initiator. No additional initiator is required. A uniformly coated shell of appropriate thickness is grown in situ on the surface of the core. If the reaction temperature is too low, the growth rate will be too slow. If the reaction temperature is too high or an additional initiator is added, there is a risk of overgrowth and agglomeration of the core-shell structure.
[0152] According to a preferred embodiment of the present invention, the drilling fluid further comprises a drilling fluid emulsifier.
[0153] According to a preferred embodiment of the present invention, the type of drilling fluid emulsifier can be selected according to the type of base fluid; based on a volume of 100 mL of the base fluid, the content of the emulsifier is 2-7 g, preferably 3-6 g.
[0154] According to a preferred embodiment of the present invention, the drilling fluid emulsifier is a polyester amide ether emulsifier and / or an emulsifier composition.
[0155] According to a preferred embodiment of the present invention, the polyesteramide ether emulsifier has the structure shown in Formula VIII: Formula VIII; In Equation VIII, R 1 C 10 -C 30 Saturated or unsaturated alkyl groups, preferably C 10 -C 20 Saturated or unsaturated alkyl groups, more preferably C10. 13 -C 17 Saturated or unsaturated alkyl groups; R 2 The substituents shown in Formula IX or -NH-; Formula IX; In equations VIII and IX, R 3 It is -CH2- or -CH(CH3)-, x is 1 or 2, and y is an integer from 2 to 10, specifically 2, 3, 4, 5, 6, 7, 8, 9 or 10.
[0156] In one specific embodiment of the present invention, the emulsifier is prepared according to Example 1 of Chinese Patent Application No. CN202011569330.4.
[0157] In one specific embodiment of the present invention, the drilling fluid preferably further includes an alkali activity regulator, preferably calcium oxide; based on a drilling fluid volume of 100 mL, the calcium oxide content in the drilling fluid is 2-4 g, preferably 2.5-4 g, and more preferably 3 g. In the present invention, the alkali activity regulator is added to adjust the alkali activity and promote emulsification.
[0158] According to a preferred embodiment of the present invention, the drilling fluid further comprises a density modifier. The density modifier can be selected from a wide range of types; various commonly used density modifiers are applicable to the present invention. Preferably, it is selected from at least one of barite, iron ore powder, ilmenite powder, galena powder, and limestone powder, with barite being the most preferred. The density of the drilling fluid can be adjusted by adding a weighting agent; the density of the drilling fluid is preferably 1-2 g / cm³. 3 For example, 1.6 g / cm 3 .
[0159] According to a preferred embodiment of the present invention, the emulsifier composition comprises a polyamine oligomer, a polyhydroxy oligomer, and a solvent.
[0160] In this invention, polyamine oligomers and polyhydroxy oligomers are used together as an emulsifier composition. Polyhydroxy oligomers have good emulsion stability, while polyamine oligomers have good solid-phase wetting effect. At the same time, the benzene ring structure in both oligomers can improve temperature resistance, and the hydroxyl and amine groups enhance their surface activity and maintain emulsion stability. The oligomeric structure provides multiple adsorption sites, which allows the emulsifier composition to be anchored and adsorbed at the oil-water interface, resulting in a more compact arrangement and further ensuring its stability at high temperatures.
[0161] According to a preferred embodiment of the present invention, based on the weight of the emulsifier composition, the content of the polyhydroxy oligomer is 40-50 wt%, preferably 42-48 wt%; the content of the polyamine oligomer is 30-40 wt%, preferably 32-38 wt%; and the content of the solvent is 10-30 wt%, preferably 14-24 wt%.
[0162] According to a preferred embodiment of the present invention, the particle size of the emulsifier composition is 5-6 μm, for example, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6 μm, or any range between the two, preferably 5.4-5.8 μm. In this invention, the particle size of the emulsifier composition is obtained by calculating the average particle size of 30 randomly selected particles in the field of view of an optical microscope.
[0163] In this invention, preferably, the emulsifier composition has a smaller particle size, which can improve the stability of the emulsifier composition and increase the demulsification voltage of the emulsifier composition.
[0164] According to a preferred embodiment of the present invention, the number-average molecular weight of the polyhydroxy oligomer is 1800-5000 g / mol, for example, 1800 g / mol, 2000 g / mol, 2200 g / mol, 2400 g / mol, 2600 g / mol, 2800 g / mol, 3000 g / mol, 3200 g / mol, 3400 g / mol, 3600 g / mol, 3800 g / mol, 4000 g / mol, 4200 g / mol, 4400 g / mol, 4500 g / mol, 4600 g / mol, 4800 g / mol, 5000 g / mol, or any range between the two, preferably 2400-4500 g / mol.
[0165] In this invention, the number-average molecular weight of the polyhydroxy oligomer meets the above-mentioned range, which helps to improve the solubility and temperature resistance of the polyhydroxy oligomer. If the number-average molecular weight is too high, the solubility of the polyhydroxy oligomer is poor and the prepared product is difficult to separate. If the number-average molecular weight is too low, the temperature resistance of the polyhydroxy oligomer is poor and it is difficult to meet the working requirements of high-temperature drilling fluid.
[0166] According to a preferred embodiment of the present invention, the hydroxyl value of the polyhydroxy oligomer is 210-600 mg KOH / g, for example, 210 mg KOH / g, 220 mg KOH / g, 240 mg KOH / g, 250 mg KOH / g, 260 mg KOH / g, 280 mg KOH / g, 300 mg KOH / g, 320 mg KOH / g, 340 mg KOH / g, 360 mg KOH / g, 380 mg KOH / g, 400 mg KOH / g, 420 mg KOH / g, 440 mg KOH / g, 460 mg KOH / g, 480 mg KOH / g, 500 mg KOH / g, 600 mg KOH / g, or any range between the two, preferably 240-500 mg KOH / g. In the present invention, the polyhydroxy oligomer contains a certain amount of hydroxyl value, which helps to improve its surface activity and maintain the stability of the emulsion.
[0167] According to a preferred embodiment of the present invention, the structural unit of the polyhydroxy oligomer contains at least one phenolic hydroxyl group, at least one amino group, and at least one alcoholic hydroxyl group. In this invention, the polyhydroxy oligomer is predominantly composed of C-C and CN bonds, which, compared to amide bonds, can improve the high-temperature hydrolysis resistance of the emulsifier. The presence of hydroxyl and amino groups enhances its surface activity, and the oligomeric structure provides multiple adsorption sites. Therefore, when used as an emulsifier, it exhibits good high-temperature hydrolysis resistance, emulsion stability, and biodegradability.
[0168] According to a preferred embodiment of the present invention, the polyhydroxy oligomer comprises a structural unit A from an alkylphenol and a structural unit B from an alkanolamine, wherein two adjacent structural units A are connected by an alkylene group having 1-6 carbon atoms, and structural unit B is connected to the benzene ring of structural unit A by an alkylene group having 1-6 carbon atoms.
[0169] According to a preferred embodiment of the present invention, the polyhydroxy oligomer comprises structural units shown in Formula III and / or Formula IV, wherein the benzene rings between two adjacent structural units are connected by R5. Formula III; Formula IV; In Formulas III and IV, R1 is a saturated or unsaturated hydrocarbon group with 8-15 carbon atoms, R2 is an alkylene group with 1-3 carbon atoms, R3 is H, hydroxymethyl, hydroxyethyl, aminomethyl or aminoethyl, and R4 and R5 are each independently an alkylene group with 1-6 carbon atoms.
[0170] According to a preferred embodiment of the present invention, based on the weight of the polyhydroxy oligomer, the content of structural unit A from alkylphenol is 50-70 wt%, preferably 55-65 wt%; the content of alkylene with 1-6 carbon atoms is 10-20 wt%, preferably 10-15 wt%; and the content of structural unit B from alkanolamine is 10-40 wt%, preferably 20-35 wt%.
[0171] According to a preferred embodiment of the present invention, the number average molecular weight of the polyamine oligomer is 4000-10000 g / mol, for example 4000 g / mol, 4500 g / mol, 5000 g / mol, 5500 g / mol, 6000 g / mol, 6500 g / mol, 7000 g / mol, 7500 g / mol, 8000 g / mol, 8500 g / mol, 9000 g / mol, 9500 g / mol, 10000 g / mol, or any range before or after these two, preferably 5000-9000 g / mol.
[0172] According to a preferred embodiment of the present invention, the amine value of the polyamine oligomer is 400-1000 mg KOH / g, for example, 400 mg KOH / g, 450 mg KOH / g, 500 mg KOH / g, 550 mg KOH / g, 600 mg KOH / g, 650 mg KOH / g, 700 mg KOH / g, 750 mg KOH / g, 800 mg KOH / g, 850 mg KOH / g, 900 mg KOH / g, 950 mg KOH / g, 1000 mg KOH / g, or any range between the two, preferably 500-900 mg KOH / g.
[0173] In this invention, preferably, the amine value of the polyamine oligomer meets the above-mentioned range, which helps to improve the solubility and temperature resistance of the polyamine oligomer.
[0174] According to a preferred embodiment of the present invention, the hydroxyl value of the polyamine oligomer is 100-300 mgKOH / g, preferably 100-220 mgKOH / g, and more preferably 150-220 mgKOH / g.
[0175] According to a preferred embodiment of the present invention, the structural unit of the polyamine oligomer contains at least one phenolic hydroxyl group and at least one amino group.
[0176] According to a preferred embodiment of the present invention, the polyamine oligomer comprises a structural unit A derived from an alkylphenol and a structural unit C derived from a polyamine; two adjacent structural units A are connected by alkylene groups having 1-6 carbon atoms, and the two ends of structural unit C are respectively connected to the benzene rings of the two structural units A by alkylene groups having 1-6 carbon atoms.
[0177] According to a preferred embodiment of the present invention, based on the weight of the polyamine oligomer, the content of structural unit A from alkylphenol is 50-60 wt%, preferably 50-55 wt%; the content of alkylene with 1-6 carbon atoms is 5-15 wt%, preferably 5-10 wt%; and the content of structural unit C from polyamine is 25-45 wt%, preferably 35-45 wt%.
[0178] According to a preferred embodiment of the present invention, the polyamine is selected from at least one of diethylenetriamine, triethylenetetramine, and tetraethylenepentamine.
[0179] According to a preferred embodiment of the present invention, in the polyamine oligomer, alkylene groups having 1-6 carbon atoms are respectively connected to the para position of R1 on the benzene ring of structural unit A and the ortho position of R1 on the adjacent benzene ring of structural unit A.
[0180] According to a preferred embodiment of the present invention, the method for producing the polyhydroxy oligomer includes: (A) In the presence of an acidic catalyst, alkylphenol and a first aldehyde are brought into contact to carry out a first condensation reaction; (B) Contact the system after the reaction in step (A) with an alcohol amine and a second aldehyde to carry out a second condensation reaction; In step (A), the molar ratio of alkylphenol to alkanolamine in step (B) is 1:0.9-1.1.
[0181] In this invention, the preparation method of the polyhydroxy oligomer is simple, the raw materials are widely available, the number-average molecular weight and hydroxyl value of the obtained polyhydroxy oligomer are controllable, and the emulsion stability of the product is good.
[0182] In this invention, preferably, the first condensation reaction and the second condensation reaction are carried out in the presence of an organic solvent. The type and amount of the organic solvent are not particularly limited, as long as the first and second condensation reactions proceed smoothly. Preferably, it is selected from at least one of white oil, diesel oil, and biomass synthesis base liquid, and more preferably, a biomass alcohol ether base liquid.
[0183] In this invention, preferably, a biomass alcohol ether-based liquid is used as a solvent. The resulting polyhydroxy oligomers and polyamine oligomers can be directly used to formulate emulsifiers without additional purification and separation. The biomass alcohol ether-based liquid can be the biomass alcohol ether of CN201610243688.5, and the entire above application is incorporated herein by reference.
[0184] According to a preferred embodiment of the present invention, the amount of the organic solvent is 30-50 wt% of the total reactants of the first condensation reaction and the second condensation reaction.
[0185] According to a preferred embodiment of the present invention, in step (A), the molar ratio of the alkylphenol to the first aldehyde is 1:0.5-0.8, for example 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, or any range between the two, preferably 1:0.5-0.7.
[0186] According to the present invention, preferably, the first aldehyde and the second aldehyde are each independently an aldehyde having 1-6 carbon atoms and its oligomers, preferably selected from at least one of paraformaldehyde, acetaldehyde, propionaldehyde and butyraldehyde, and more preferably paraformaldehyde. In the present invention, the first aldehyde and the second aldehyde may be the same or different.
[0187] According to the present invention, preferably, the alkylphenol has the structure shown in Formula V. Formula V; In formula V, R1 is a saturated or unsaturated hydrocarbon group with 8-15 carbon atoms.
[0188] More preferably, the alkylphenol is cashew phenol and / or urushiol, and even more preferably cashew phenol. Cashew phenol has a suitable long carbon chain, which helps to improve the emulsification effect and stability of polyhydroxy oligomers. It also has the advantages of being widely available, easy to obtain, low cost, environmentally friendly, biodegradable, and highly reactive. However, excessively long carbon chains can lead to excessive steric hindrance, which may hinder the reaction.
[0189] In this invention, the conditions for the first condensation reaction and the second condensation reaction can be selected from a wide range. Conventional condensation reaction conditions can be applied to this invention. The following is an illustrative description, but it does not limit the scope of this invention.
[0190] According to a preferred embodiment of the present invention, in step (A), the first condensation reaction conditions include: a reaction temperature of 70-100°C, preferably 75-85°C; and a reaction time of 2-5 h, preferably 3-4 h.
[0191] According to a preferred embodiment of the present invention, the type and amount of the acidic catalyst can be selected from a wide range, and it is a conventional acidic catalyst in the art. The acidic catalyst is selected from at least one of hydrochloric acid, sulfuric acid, dodecylbenzenesulfonic acid, aminosulfonic acid, and oxalic acid.
[0192] According to a preferred embodiment of the present invention, the amount of acidic catalyst used is 0.5-1 wt% of the amount of alkylphenol used, preferably 0.6-0.8 wt%.
[0193] According to a preferred embodiment of the present invention, in step (B), the molar ratio of the alkanolamine to the second aldehyde is 1:0.9-1.05, preferably 1:0.95-1.
[0194] According to a preferred embodiment of the present invention, the range of types of alkanolamines is relatively wide, and the alkanolamines are selected from at least one of ethanolamine, diethanolamine, isopropanolamine and hydroxyethyl ethylenediamine.
[0195] According to a preferred embodiment of the present invention, the molar ratio of alkylphenol in step (A) to alkanolamine in step (B) is 1:0.95-1.05.
[0196] According to a preferred embodiment of the present invention, in step (B), the conditions for the second condensation reaction include: a reaction temperature of 60-90°C, preferably 70-80°C; and a reaction time of 1-4 h, preferably 2-3 h.
[0197] According to a preferred embodiment of the present invention, the method for preparing the polyamine oligomer includes: (a) In the presence of an amine catalyst, an alkylphenol is brought into contact with a third aldehyde to carry out a third condensation reaction; (b) The system after the reaction in step (a) is brought into contact with a polyamine and a fourth aldehyde to carry out a fourth condensation reaction.
[0198] In this invention, the polyamine oligomers and polyhydroxy oligomers contained in the emulsifier composition exist in a non-gel emulsion form. After the reaction is completed, they can be used directly as emulsifiers without purification and separation. The operation steps are simple and the product is highly practical.
[0199] According to a preferred embodiment of the present invention, in step (a), the molar ratio of the alkylphenol to the third aldehyde is 1:1-1.2, preferably 1:1.05-1.15.
[0200] In this invention, the conditions for the third and fourth condensation reactions can be selected from a wide range. Conventional condensation reaction conditions are applicable to this invention. The following is an illustrative description, but it does not limit the scope of this invention.
[0201] According to a preferred embodiment of the present invention, in step (a), the conditions for the third condensation reaction include: a reaction temperature of 90-110°C, preferably 95-105°C; and a reaction time of 2-5 h, preferably 3-4 h.
[0202] According to a preferred embodiment of the present invention, the type and amount of the amine catalyst can be selected from a wide range, and it is a conventional amine catalyst in the art. The amine catalyst is selected from at least one of triethylamine, diethylamine and diisopropylethylamine.
[0203] According to a preferred embodiment of the present invention, the amount of the amine catalyst used is 0.5-1 wt% of the amount of alkylphenol used, preferably 0.6-0.8 wt%.
[0204] According to a preferred embodiment of the present invention, in step (b), the molar ratio of the polyamine to the fourth aldehyde is 1:1.1-1.3, preferably 1:1.15-1.25.
[0205] In this invention, preferably, the third aldehyde and the fourth aldehyde are each independently an aldehyde with 1-6 carbon atoms and its oligomers, preferably selected from at least one of paraformaldehyde, acetaldehyde, propionaldehyde and butyraldehyde, more preferably paraformaldehyde, and the third aldehyde and the fourth aldehyde may be the same or different.
[0206] According to a preferred embodiment of the present invention, the molar ratio of alkylphenol in step (a) to polyamine in step (b) is 1:0.9-1.1, preferably 1:0.95-1.05.
[0207] According to a preferred embodiment of the present invention, in step (b), the conditions for the fourth condensation reaction include: a reaction time of 70-100°C, preferably 80-90°C; and a reaction time of 1-4 hours, preferably 2-3 hours.
[0208] In this invention, preferably, the third and fourth condensation reactions are carried out in the presence of an organic solvent. The type and amount of the organic solvent can be the same as or different from the organic solvent used in the first and second condensation reactions, and is preferably a biomass alcohol ether-based liquid. Preferably, the amount of the organic solvent is 30-50 wt% of the total reactants in the third and fourth condensation reactions.
[0209] In this invention, the preparation method of the drilling fluid is not particularly limited. It can be prepared according to methods well known to those skilled in the art, and there are no special restrictions. Specifically, it can be carried out according to the following method: add gelling material, emulsifier, filtration loss reducer and plugging agent to diesel or biomass synthetic base fluid in sequence, and perform a first high-speed stirring. Then add calcium chloride aqueous solution and perform a second high-speed stirring. Then add calcium oxide and perform a third high-speed stirring. Finally, add barite to adjust the drilling fluid density and perform a fourth high-speed stirring to obtain the drilling fluid.
[0210] In a specific embodiment of the present invention, the rotation speeds of the first, second, third, and fourth high-speed stirrings are each preferably 8000-12000 r / min, more preferably 10000 r / min; the duration of the first high-speed stirring can be 10-15 min, such as 12 min; the duration of the second high-speed stirring can be 6-10 min, such as 8 min; the duration of the third high-speed stirring can be 6-15 min, such as 8 min; and the duration of the fourth high-speed stirring can be 15-25 min, such as 20 min.
[0211] In this invention, preferably, the drilling fluid provided has good compatibility due to the combined effect of components such as polymer emulsion plugging agent, core-shell structure material and emulsifier composition. It has good plugging properties, rheological stability and suspension stability in both biomass-based and diesel-based drilling fluids, and can maintain good performance under high temperature and high pressure.
[0212] All reagents used in the following examples are commercially available; potassium persulfate, dodecylphenol polyoxyethylene ether (OP-10), sodium dodecyl sulfate, sodium bicarbonate, butyl acrylate, isooctyl acrylate, and octadecyl acrylate used in the examples were purchased from Aladdin Reagent Co., Ltd.; No. 0 diesel oil is commercially available; The biomass synthesis base liquid comes from the Drilling Engineering Technology Research Institute of Sinopec Zhongyuan Petroleum Engineering Co., Ltd., and can be obtained by preparing biomass base oil according to Example 2 of the patent application number 201810743989.3. The organic bentonite was purchased from Sichuan Xinchuangneng Petroleum Engineering Technology Co., Ltd. The polyester amide ether emulsifier was provided by the Drilling Engineering Technology Research Institute of Sinopec Zhongyuan Petroleum Engineering Co., Ltd., and its main component is polyester amide ether, which was prepared according to Example 1 of Patent 202011569330.4; The filtration loss reducer was provided by the Drilling Engineering Technology Research Institute of Sinopec Zhongyuan Petroleum Engineering Co., Ltd., and its main component is humic acid amide, prepared according to Example 1 of the patent application number 202110591326.6; calcium oxide and calcium chloride were purchased from Hubei Longhai Chemical Co., Ltd. The barite was purchased from Zhengzhou Xinzheng Meijiu Industrial Co., Ltd. The asphalt-based sealing agent (sulfonated asphalt powder FT-1) was purchased from Xinxiang No. 7 Chemical Co., Ltd., Henan Province. The calcium carbonate plugging agent (ultrafine calcium carbonate QS-2) was purchased from Puyang Zhongyuan Sanli Industrial Co., Ltd.; the spherical gel was from the Drilling Engineering Technology Research Institute of Sinopec Zhongyuan Petroleum Engineering Co., Ltd., and could be prepared according to Example 3 of Chinese Patent Application No. 201410602573.1.
[0213] Example 1 Under stirring at 100 rpm, 730 parts by mass of water, 2.9 parts by mass of sodium dodecyl sulfate, 9.4 parts by mass of dodecylphenol polyoxyethylene ether, 1.9 parts by mass of sodium bicarbonate, and 175 parts by mass of butyl acrylate were added sequentially to the reactor. Emulsification was carried out under nitrogen protection for 20 min. The temperature was raised to 70℃, and 1.4 parts by mass of potassium persulfate (added as a potassium persulfate solution with a potassium persulfate mass fraction of 3%) was added dropwise through a constant pressure dropping funnel over 25 min. After reacting for 30 min, the mixture was kept at 70℃ for 2 h. Cooling to room temperature yielded a polymer emulsion blocking agent with a number-average molecular weight of 305242 g / mol, a weight-average molecular weight of 394982 g / mol, a molecular weight distribution of 1.29, and a median particle size D of 1.29. 50 It has a wavelength of 189 nm and a solid content of 19.8 wt%.
[0214] The polymer emulsion blocking agent (after drying) prepared in Example 1 was analyzed using infrared spectroscopy, and its infrared absorption spectrum is shown below. Figure 1 As shown. By Figure 1 It can be seen that 2960 cm -1 2934 cm -1 The peak at 2874 cm⁻¹ represents the absorption peak of the CH antisymmetric stretching vibrations of -CH₃ and -CH₂- in polybutyl acrylate. -1 This is caused by the CH-symmetric stretching vibrations of -CH3 and -CH2- in polybutyl acrylate, 1735 cm. -1 The peak at 1251 cm⁻¹ is the absorption peak of the C=O stretching vibration in polybutyl acrylate. -1 The absorption peak for the antisymmetric stretching vibration of COC is at 1165 cm⁻¹. -1The peak at 1165 cm⁻¹ is the absorption peak of the symmetric stretching vibration of COC. -1 The absorption peak at that location is greater than 1251 cm⁻¹ -1 The absorption peak at that point confirms that the target product, butyl acrylate polymer, has been obtained.
[0215] Figure 2 The particle size distribution diagram of the polymer emulsion plugging agent prepared in Example 1 of this invention is shown. The particle size distribution of sample D was determined according to the wet sample operation procedure of a high-performance laser particle size analyzer. 50 (Median particle size), circulating medium is distilled water, D 50 The test result was 189nm.
[0216] Example 2 Under stirring, 750 parts by mass of water, 2.6 parts by mass of sodium dodecyl sulfate, 8.7 parts by mass of dodecylphenol polyoxyethylene ether, 1.8 parts by mass of sodium bicarbonate, and 170 parts by mass of octadecyl acrylate were added sequentially to the reactor. Emulsification was carried out under nitrogen protection for 25 minutes. The temperature was then raised to 80°C, and 1.3 parts by mass of potassium persulfate (3% by mass in the potassium persulfate solution) was added dropwise through a constant-pressure dropping funnel over 25 minutes. After reacting for 30 minutes, the mixture was kept at 80°C for 2 hours. Cooling to room temperature yielded a polymer emulsion blocking agent with a number-average molecular weight of 334,326 g / mol, a weight-average molecular weight of 411,220 g / mol, a molecular weight distribution of 1.23, and a median particle size D. 50 It has a wavelength of 219 nm and a solid content of 18.9 wt%.
[0217] Example 3 Under stirring, 700 parts by mass of water, 2.7 parts by mass of sodium dodecyl sulfate, 9.6 parts by mass of dodecylphenol polyoxyethylene ether, 2.0 parts by mass of sodium bicarbonate, and 180 parts by mass of isooctyl acrylate were added sequentially to the reactor. Emulsification was carried out under nitrogen protection for 25 min. The temperature was raised to 74℃, and 1.5 parts by mass of potassium persulfate (3% by mass in the potassium persulfate solution) was added dropwise through a constant-pressure dropping funnel, completing the addition over 25 min. After reacting for 30 min, the mixture was kept at 75℃ for 2 h. Cooling to room temperature yielded a polymer emulsion blocking agent with a number-average molecular weight of 327698 g / mol, a weight-average molecular weight of 406345 g / mol, a molecular weight distribution of 1.24, and a median particle size D. 50 It has a wavelength of 216 nm and a solid content of 20.8 wt%.
[0218] Example 4 Following the method of Example 1, except that the emulsifier was changed to 2.22 parts by mass of sodium dodecyl sulfate and 9.36 parts by mass of dodecylphenol polyoxyethylene ether, while other conditions remained the same as in Example 1, a polymer emulsion blocking agent was obtained with a number-average molecular weight of 308,000 g / mol, a weight-average molecular weight of 400,000 g / mol, a molecular weight distribution of 1.3, and a median particle size D. 50 It has a wavelength of 504 nm and a solid content of 19.8 wt%.
[0219] Example 5 Following the method of Example 1, except that the emulsifier was changed to 3.2 parts by mass of sodium dodecyl sulfate and 9.6 parts by mass of dodecylphenol polyoxyethylene ether, while other conditions remained the same as in Example 1, a polymer emulsion blocking agent was obtained with a number-average molecular weight of 293,755 g / mol, a weight-average molecular weight of 391,256 g / mol, a molecular weight distribution of 1.33, and a median particle size D. 50 It has a wavelength of 216 nm and a solid content of 19.7 wt%.
[0220] Example 6 Following the method of Example 1, except that the initiator was added completely within 10 minutes, and other conditions were the same as in Example 1, a polymer emulsion blocking agent was obtained with a number-average molecular weight of 258,282 g / mol, a weight-average molecular weight of 362,189 g / mol, a molecular weight distribution of 1.4, and a median particle size D. 50 It has a wavelength of 156 nm and a solid content of 19.7 wt%.
[0221] Comparative Example 1 Following the method of Example 1, except that butyl acrylate was replaced with an equal mass of methyl methacrylate, and other conditions were the same as in Example 1, a polymer emulsion blocking agent was obtained with a number-average molecular weight of 172231 g / mol, a weight-average molecular weight of 257895 g / mol, a molecular weight distribution of 1.5, and a median particle size D. 50 It has a wavelength of 197 nm and a solid content of 19.8 wt%. It exhibits a very wide molecular weight distribution and poor polymer uniformity.
[0222] Comparative Example 2 Following the method of Example 1, except that butyl acrylate was replaced with an equal mass ratio of monomer mixture, in which the mass ratio of methyl methacrylate to butyl acrylate in the monomer mixture was 1:1, and other conditions were the same as in Example 1, a polymer emulsion blocking agent was obtained with a number-average molecular weight of 237,984 g / mol, a weight-average molecular weight of 334,562 g / mol, a molecular weight distribution of 1.406, and a median particle size D. 50 The wavelength is 196 nm, and the solid content is 19.8 wt%. The molecular weight distribution is broadened.
[0223] Comparative Example 3 Following the method of Example 1, except that dodecylphenol polyoxyethylene ether was replaced with an equal mass of sodium dodecyl sulfate, and other conditions were the same as in Example 1, a polymer emulsion blocking agent was obtained with a number-average molecular weight of 254423 g / mol, a weight-average molecular weight of 324876 g / mol, a molecular weight distribution of 1.28, and a median particle size D. 50 The wavelength is 153 nm, and the solid content is 19.7 wt%. Severe foaming occurred during the reaction process, with raw materials overflowing from the reactor, affecting production. Agglomerates were present, and the emulsion polymer showed agglomeration after prolonged storage.
[0224] Comparative Example 4 Following the method of Example 1, except that sodium dodecyl sulfate was replaced with an equal mass of dodecylphenol polyoxyethylene ether, and other conditions were the same as in Example 1, a polymer emulsion blocking agent was obtained with a number-average molecular weight of 342,725 g / mol, a weight-average molecular weight of 448,795 g / mol, a molecular weight distribution of 1.31, and a median particle size D. 50 The wavelength is 1300 nm, and the solid content is 19.7 wt%.
[0225] Comparative Example 5 Following the method of Example 1, except that the emulsifier was changed to 5.85 parts by weight of sodium dodecyl sulfate and 5.85 parts by weight of dodecylphenol polyoxyethylene ether, while other conditions remained the same as in Example 1, a polymer emulsion blocking agent was obtained with a number-average molecular weight of 238,582 g / mol, a weight-average molecular weight of 340,467 g / mol, a molecular weight distribution of 1.43, and a median particle size D. 50 The wavelength is 216 nm, and the solid content is 19.7 wt%. The reaction process still produces foam and agglomerates, and the emulsion polymer agglomerates after long-term storage.
[0226] Comparative Example 6 Following the method of Example 1, except that the emulsifier was changed to 3.5 parts by mass of sodium dodecyl sulfate and 8.8 parts by mass of dodecylphenol polyoxyethylene ether, while other conditions remained the same as in Example 1, a polymer emulsion blocking agent was obtained, wherein the number average molecular weight of the acrylate polymer was 247,550 g / mol, the weight average molecular weight was 346,571 g / mol, the molecular weight distribution was 1.4, and the median particle size D of the polymer emulsion blocking agent was... 50 It has a wavelength of 175 nm and a solid content of 19.6 wt%.
[0227] Comparative Example 7 Following the method of Example 1, except that the emulsifier was changed to 1.9 parts by mass of sodium dodecyl sulfate and 10.6 parts by mass of dodecylphenol polyoxyethylene ether, while other conditions remained the same as in Example 1, a polymer emulsion blocking agent was obtained, wherein the number average molecular weight of the acrylate polymer was 314902 g / mol, the weight average molecular weight was 434565 g / mol, the molecular weight distribution was 1.38, and the median particle size D of the polymer emulsion blocking agent was... 50 It has a wavelength of 620 nm and a solid content of 19.8 wt%.
[0228] Example 1 of core-shell structure material preparation (I) Dissolve 5g of citric acid in 20mL of deionized water, then prepare 20mL of a mixed solution of 1mol / L CaCl2 and 1mol / L FeSO4 and maintain the solution temperature at 0-2℃. Add the above citric acid solution dropwise, stirring continuously during the dropwise addition. Add the solution dropwise at a uniform rate of 0.2mL / s. After the dropwise addition is complete, continue stirring for 15min to carry out the precipitation reaction. Then filter, wash and dry the precipitate to obtain the precursor. Keep the filtrate and calcine the precursor at 450℃ for 2h to obtain oxygen vacancy type doped transition metal oxide. (II) The above filtrate was used as a carboxyl source and dissolved in 20 mL of deionized water at 40 °C. Then, 0.5 g of oxygen vacancy-type doped transition metal oxide was added and dispersed evenly. 1 g of trimethylolpropane was added and stirred thoroughly. The mixture was then placed in an environment of 40 °C and 0.5 MPa for 2 h to carry out a polycondensation reaction to form a hyperbranched polyester shell (HBP) to obtain core-shell structure material D1. The molar ratio of doped metal to transition metal was 1:1.
[0229] The average particle size of the core is 500 nm, the average thickness of the shell is 20 nm, the coverage rate is 100%, and the mass ratio of the shell to the core is 1:4.
[0230] Figure 3 These are SEM images and EDS elemental distribution maps of Example 1 of core-shell structured material preparation (data in the figures are atomic percentages). Figure 4 These are SEM images and EDS elemental distribution maps of uncoated doped transition metal oxides from Example 1 of core-shell structure material preparation. Figure 3 and Figure 4 It can be seen that C and O elements are widely distributed on the surface of the rod-shaped nano-core-shell structured material, and their overall surface content is much higher than that of Fe and Ca elements, indicating that the hyperbranched polymer shell has a large-area coating of metal oxides.
[0231] Figure 5 The XPS peak intensity fitting curve of the product from Example 1, used for the preparation of core-shell structured materials, was obtained through software analysis. Figure 5In core-shell structured materials, the vacancy oxygen peak area in the core accounts for 34% of the total peak area.
[0232] Example 1 of Emulsifier Composition Preparation Example 1 of preparation of polyhydroxy oligomers (A) In the presence of a biomass alcohol ether base liquid, cashew phenol, paraformaldehyde, and dodecylbenzene sulfonic acid were mixed and reacted at 80°C for 3.5 h. The molar ratio of cashew phenol to paraformaldehyde was 1:0.6, and the amount of dodecylbenzene sulfonic acid added was 0.7 wt% of cashew phenol. (B) Diethanolamine and paraformaldehyde with a molar ratio of 1:0.98 were added to the system after the reaction in step (A). The molar ratio of cashew phenol in step (A) to diethanolamine in step (B) was 1:1. The amount of biomass alcohol ether base liquid used was 40 wt% of the total weight of cashew phenol, paraformaldehyde and diethanolamine. The reaction was carried out at 75°C for 2.4 h to obtain a reaction product containing polyhydroxy oligomer A1. The reaction product was separated to obtain polyhydroxy oligomer A1, and its number average molecular weight was tested to be 3287 g / mol.
[0233] Figure 6 The pH-titrate volume curve recorded during the hydroxyl value testing process of Example 1 for the preparation of polyhydroxy oligomers was used. The prepared polyhydroxy oligomer A1 was directly used for testing. The blank sample curve was subtracted from the titration curve. Figure 6 Curve analysis revealed that the hydroxyl value of the polyhydroxy oligomer was 325 mg KOH / g.
[0234] The sample was 0.0522 g, and the hydrochloric acid concentration was 0.05105 mol / L. The titration volume of sample V2 was 39.56 mL, and the titration volume of V1 was 32.11 mL.
[0235] The internal standard V2 was titrated in a volume of 28.22 mL, and the internal standard V1 was titrated in a volume of 14.84 mL.
[0236] The calculated hydroxyl value is 325.344 mg KOH / g.
[0237] Figure 7 The infrared spectroscopy results of Example 1 for the preparation of polyhydroxy oligomers were obtained by... Figure 7 It can be seen that the 3200-3600 cm⁻¹ hydroxyl peak (characteristic of polyhydroxyl groups), the 1500-1600 cm⁻¹ benzene ring peak (cashew phenol skeleton), and the 1050-1250 cm⁻¹ CO / CN peak (diethanolamine reaction product) are all consistent with the synthetic design and are key evidence for the target product. Among them, the S=O peak can be interpreted as residual dodecylbenzenesulfonic acid (DBSA), which is an acceptable impurity signal.
[0238] Example 1 of preparation of polyamine oligomers (a) In the presence of a biomass alcohol ether base liquid, cashew phenol, paraformaldehyde, and triethylamine were mixed and reacted at 100°C for 3.5 h. The molar ratio of cashew phenol to paraformaldehyde was 1:1.1, and the amount of triethylamine added was 0.6 wt% of cashew phenol. (b) Add diethylenetriamine and paraformaldehyde in a molar ratio of 1:1.2 to the system after the reaction in step (a). The molar ratio of cashew phenol in step (a) to diethylenetriamine in step (b) is 1:1. The amount of biomass alcohol ether base liquid used is 40 wt% of the total weight of cashew phenol, paraformaldehyde and diethylenetriamine. React at 85°C for 2.5 h. Separate the reaction products to obtain polyamine oligomer B1.
[0239] The number-average molecular weight of the polyamine oligomer is 6821 g / mol, the amine value is 632 mg KOH / g, and the hydroxyl value is 189 mg KOH / g.
[0240] Drilling fluid application example 1 Base solution: 255 mL of No. 0 diesel oil (85% by volume); 45 mL of 20% calcium chloride aqueous solution (15% by volume).
[0241] Based on the total volume of diesel and calcium chloride aqueous solution: 3% (by weight / volume) of organic bentonite, 6% (by weight / volume) of polyester amide ether emulsifier, 4% (by weight / volume) of humic acid amide filtration reducer, and 2% (by weight / volume) of the polymer emulsion plugging agent prepared in Example 1 were added sequentially to the diesel. The mixture was stirred at high speed (10000 r / min, the same below) for 12 min, then calcium chloride aqueous solution was added and stirred at high speed for 8 min, followed by 3% (by weight / volume) of calcium oxide and stirred at high speed for 8 min. Finally, barite was added to adjust the drilling fluid density to 1.6 g / cm³. 3 Stir at high speed for 20 minutes to obtain drilling fluid.
[0242] Figure 8 This is a filter cake photograph from Example 1 of drilling fluid application. Figure 9 This is a scanning electron microscope (SEM) image of the filter cake from Example 1 of drilling fluid application. Images (a) and (b) are magnified 200x, and image (c) is magnified 500x. Figure 8 and Figure 9 As can be seen, the surface of the plugging agent in this application example is a film-like layer, which is relatively flat and dense, forming a dense sealing and protection layer under the action of pressure difference.
[0243] Drilling fluid application example 2 The drilling fluid was prepared according to the method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 2 of equal mass was used instead of the plugging agent prepared in Example 1.
[0244] Drilling fluid application example 3 The drilling fluid was prepared according to the method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 3 of equal mass was used instead of the plugging agent prepared in Example 1.
[0245] Drilling fluid application example 4 The drilling fluid was prepared according to the method of Drilling Fluid Application Example 1, except that an equal mass of biomass synthetic base fluid was used to replace No. 0 diesel.
[0246] Drilling fluid application example 5 The drilling fluid was prepared according to the method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 4 of equal mass was used instead of the plugging agent prepared in Example 1.
[0247] Drilling fluid application example 6 The drilling fluid was prepared according to the method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 5 of equal mass was used instead of the plugging agent prepared in Example 1.
[0248] Drilling fluid application example 7 The drilling fluid was prepared according to the method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 6 of equal mass was used instead of the plugging agent prepared in Example 1.
[0249] Drilling fluid comparison example 1 The drilling fluid was prepared according to the method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was not added.
[0250] Drilling fluid comparison example 2 The drilling fluid was prepared according to the method of Drilling Fluid Application Example 4, except that the polymer emulsion plugging agent prepared in Example 1 was not added.
[0251] Drilling fluid comparison example 3 The drilling fluid was prepared according to the method of Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was replaced with 2% by volume bitumen plugging agent.
[0252] Drilling fluid comparison example 4 The drilling fluid was prepared according to the method of Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was replaced with a calcium carbonate plugging agent at a mass-volume ratio of 3%.
[0253] Drilling fluid comparison example 5 The drilling fluid was prepared according to the method of Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was replaced with 2% by volume of spherical gel.
[0254] Drilling fluid comparison example 6 The drilling fluid was prepared according to the preparation method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was replaced with the plugging agent prepared in Comparative Example 1.
[0255] Drilling fluid comparison example 7 The drilling fluid was prepared according to the preparation method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was replaced with the plugging agent prepared in Comparative Example 2.
[0256] Drilling fluid comparison example 8 The drilling fluid was prepared according to the preparation method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was replaced with the plugging agent prepared in Comparative Example 3.
[0257] Drilling fluid comparison example 9 The drilling fluid was prepared according to the preparation method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was replaced with the plugging agent prepared in Comparative Example 4.
[0258] Drilling fluid comparison ratio 10 The drilling fluid was prepared according to the preparation method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was replaced with the plugging agent prepared in Comparative Example 5.
[0259] Drilling fluid comparison example 11 The drilling fluid was prepared according to the preparation method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was replaced with the plugging agent prepared in Comparative Example 6.
[0260] Drilling fluid comparison example 12 The drilling fluid was prepared according to the preparation method of Drilling Fluid Application Example 1, except that the polymer emulsion plugging agent prepared in Example 1 was replaced with the plugging agent prepared in Comparative Example 7.
[0261] Test Example 1 The drilling fluids prepared in the drilling fluid application examples and drilling fluid comparative examples were aged at 130℃ for 16 hours according to the national standard GB / T 16783.2-2012 "Field Testing of Drilling Fluids for Petroleum and Natural Gas Industry - Part 2: Oil-based Drilling Fluids". The rheological properties were tested at 60℃, the demulsification voltage was tested at 50℃, and the high-temperature and high-pressure filtration loss was measured at 130℃. The test results are shown in Table 1.
[0262] Table 1. Performance test results of drilling fluids prepared in the embodiments and comparative examples of the present invention.
[0263] In Table 1, AV is the apparent viscosity, PV is the plastic viscosity, YP is the dynamic shear force, Gel is the initial and final shear, ES is the demulsification voltage, HTHP is the high-temperature and high-pressure filtration loss, and YP / PV is the dynamic plasticity ratio.
[0264] As shown in Table 1, the drilling fluid prepared using the polymer emulsion plugging agent prepared in the embodiments of the present invention, in drilling fluid application examples 1-4, with an addition of 2% (mass-volume ratio) of plugging agent, aged at 130℃ for 16h, has a high-temperature and high-pressure filtration loss of 2.2-2.8 mL and a high-temperature and high-pressure mud cake thickness of about 1 mm.
[0265] Compared to Comparative Example 1, the diesel-based drilling fluid application example 1 showed that adding 2% of Example 1 reduced the high-temperature and high-pressure filtration loss by 57.7% (from 5.2 mL to 2.2 mL), increased the demulsification voltage by 40.9% (from 550 V to 775 V), increased the dynamic-plastic ratio by 0.29 to 0.34, and reduced the high-temperature and high-pressure mud cake thickness by 2.5 mm to 0.9 mm. The biomass-based drilling fluid application example 4 showed that compared to Comparative Example 2, adding 2% of Example 1 reduced the high-temperature and high-pressure filtration loss by 63.1% (from 7.6 mL to 2.8 mL), increased the demulsification voltage by 9.0% (from 520 V to 590 V), increased the dynamic-plastic ratio by 0.34 to 0.41, and reduced the high-temperature and high-pressure mud cake thickness by 2.7 mm to 1.0 mm.
[0266] Compared with drilling fluid comparative examples 3-5, the addition of the polymer emulsion plugging agent resulted in lower high-temperature and high-pressure filtration loss in drilling fluid application example 1, and significantly improved mud cake quality, resulting in a thinner, tougher, and denser mud cake. In summary, it can be seen that the polymer emulsion plugging agent for oil-based drilling fluids prepared using this invention exhibits good plugging properties, rheological stability, and suspension stability, good compatibility, and is suitable for diesel-based and biomass-based drilling fluids.
[0267] Test Example 2 Plugging agents can effectively prevent the solid and liquid phases of drilling fluid from entering the oil and gas reservoir, reducing potential factors that could cause damage. The test method for evaluating the plugging effect of plugging agents is as follows: Add 10 cm of sand with a particle size of 40-60 mesh to the cylindrical chamber of a visual medium-pressure sand bed filtration analyzer, compact and level it, then slowly add 300 mL of drilling fluid. Under a pressure of 0.7 MPa, measure the depth of the filtrate entering the sand bed; the test results are shown in Table 2.
[0268] Table 2 Comparison of the penetration depth of the plugging agents prepared in the embodiments and comparative examples of the present invention into the sand bed in the drilling fluid.
[0269] Note: The length of the sand bed is 10 cm.
[0270] By comparing the penetration depths of drilling fluid application example 1 and drilling fluid comparison example 1, as well as drilling fluid application example 4 and drilling fluid comparison example 2, it can be seen that diesel-based drilling fluid and biomass synthetic-based drilling fluid, after the addition of 2wt% polymer emulsion plugging agent, have good plugging effects. They effectively prevent the penetration of diesel-based and biomass synthetic-based drilling fluids within 30 minutes, and can effectively plug the micro-fractures / pores in the sand bed, reduce the amount and depth of drilling fluid penetration in the sand bed, help to achieve plugging and leakage prevention, and meet the drilling requirements of hard, brittle and fractured formations with bedding and micro-fracture development.
[0271] As can be seen from the above embodiments, the polymer emulsion plugging agent prepared under optimal conditions by the method provided by the present invention has excellent plugging performance. It can form a dense protective film on the filter cake, helping to form a thin and dense mud cake, reducing filtration loss under high temperature and high pressure. Its plugging ability is superior to commonly used plugging agents (asphalt-based, calcium carbonate-based, spherical gel), and it has good compatibility, making it suitable for drilling fluids such as diesel-based and biomass-based drilling fluids. In the preparation method of the polymer emulsion plugging agent provided by the present invention, it is mainly obtained by emulsion polymerization reaction using acrylate soft monomers. The present invention uses water as a reaction solvent, the reaction conditions are mild, the production process is simple and easy to implement, the production process does not generate wastewater or waste residue, and the overall cost is low. The product has a significant price advantage, high cost performance, and is suitable for large-scale promotion and application.
[0272] Test Example 3: Filter cake permeability reduction rate verifies film formation effect Polymer emulsion plugging agents can form an effective protective film on filter cake, enhancing its compactness, reducing filtration loss under high temperature and pressure, and simultaneously exhibiting good elastic deformation properties to improve filter cake strength. The filter cake permeability of the polymer emulsion plugging agent was tested using the filter cake permeability reduction rate test to verify the film-forming and plugging effect. The experimental method referred to the drilling fluid and completion fluid filter cake performance testing method (Q / SH0364-2010).
[0273] Experimental methods: ①Preparation of high temperature and high pressure filter cake Biomass-based drilling fluid formulation #1: 255mL biomass-based fluid + 45mL water + CaCl2 (30wt%) + 3% organic soil (mass-volume ratio) + 6% emulsifier (mass-volume ratio) + 4% filtration reducer (mass-volume ratio) + 3% CaO (mass-volume ratio) + barite (ρ=1.6g / cm³). 3 ); Biomass-based drilling fluid formulation 2#: Formulation 1# + 2wt% polymer emulsion plugging agent from Example 1; The above formulas were aged at 130°C for 16 hours and then prepared into filter cakes using a high-temperature and high-pressure filtration apparatus. ② Filter cake permeability measurement Gently pour out the drilling fluid from the high-temperature and high-pressure cylinder, inject a small amount of biomass synthesis base liquid along the inner wall of the cylinder, gently shake it, and then pour out the biomass synthesis base liquid; then inject biomass synthesis base liquid to the mark, assemble the instrument, measure the filtration loss of the biomass synthesis base liquid by the high-temperature and high-pressure filter cake, record the filtration loss volume over 30 minutes, the measurement temperature is 130℃, and the pressure difference is 0.7MPa.
[0274] After disassembling the device, the filter cake was removed and its thickness was measured using a drilling fluid filter cake tester. Five points were measured for each filter cake, and the average value was taken. The results are shown in Table 3.
[0275] The filter cake permeability is calculated according to formula (1), and the filter cake permeability reduction rate is calculated according to formula (2).
[0276] (1) K: Average permeability of the filter cake, 10 -3 μm 2 ; q: The volume of diesel fuel lost through filtration within 30 minutes, in mL; l: Average thickness of the filter cake, mm; μ: Viscosity of biomass synthesis base liquid at the experimental temperature, mPa·s; A: Filtration area, cm² 2 ; ΔP: Test pressure difference, MPa; (2) Table 3. Filter cake permeability measurement
[0277] The experimental results show that the high-temperature and high-pressure filter cake with the addition of polymer emulsion plugging agent is more compact, and the permeability reduction rate reaches 85.75%. This indicates that the polymer emulsion plugging agent can easily form a protective film on the surface of the filter cake of biomass synthetic drilling fluid, improve the compactness of the filter cake, reduce the permeability of the drilling fluid, and thus prevent the transmission of liquid phase pressure. This is beneficial to increasing the extension pressure and reopening pressure of nano- and micro-fractures, thereby achieving the purpose of pre-plugging and preventing leakage.
[0278] Test Example 4 The drilling fluids prepared in the drilling fluid application examples and drilling fluid comparative examples were aged at 200℃ for 16 hours according to the national standard GB / T 16783.2-2012 "Field Testing of Drilling Fluids for Petroleum and Natural Gas Industry - Part 2: Oil-based Drilling Fluids". The rheological properties were tested at 60℃, the demulsification voltage was tested at 50℃, and the high-temperature and high-pressure filtration loss was measured at 180℃. The test results are shown in Table 4.
[0279] Drilling fluid application example 8 Solution: 255 mL of No. 0 biomass synthesis base liquid (85% by volume); 45 mL of 30 wt% calcium chloride aqueous solution (15% by volume).
[0280] Based on the total volume of the biomass synthesis base fluid and the calcium chloride aqueous solution: 4% (by mass / volume ratio, i.e., 4 g / 100 mL, the meaning of mass / volume ratio is the same below) of organic bentonite, 5% (by mass / volume ratio) of the emulsifier composition preparation example 1, 4% (by mass / volume ratio) of the core-shell structure material preparation example 1, and 2% (by mass / volume ratio) of the polymer emulsion plugging agent prepared in Example 1 were added sequentially to the biomass synthesis base fluid. The mixture was stirred at high speed (10000 r / min, the same below) for 12 min, then the calcium chloride aqueous solution was added and stirred at high speed for 8 min, followed by 3% (by mass / volume ratio) of calcium oxide and stirred at high speed for 8 min. Finally, barite was added to adjust the drilling fluid density to 1.7 g / cm³. 3 Stir at high speed for 20 minutes to obtain drilling fluid.
[0281] Drilling fluid application example 9 The drilling fluid was prepared according to the method of Drilling Fluid Application Example 8, except that the polymer emulsion plugging agent prepared in Example 2 of equal mass was used instead of the plugging agent prepared in Example 1.
[0282] Drilling fluid application example 10 The drilling fluid was prepared according to the method of Drilling Fluid Application Example 8, except that the polymer emulsion plugging agent prepared in Example 3 of equal mass was used instead of the plugging agent prepared in Example 1.
[0283] Table 4
[0284] As can be seen from the results in Table 4, the plugging agent of the present invention has good compatibility with the core-shell structure material and emulsifier composition. The prepared drilling fluid has the characteristics of low viscosity and high shear rate. It can also maintain a low high-temperature and high-pressure filtration loss and a high demulsification voltage at high temperatures, which can meet the requirements of high-temperature downhole operations.
[0285] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A polymer emulsion plugging agent, characterized in that, The polymer in the polymer emulsion plugging agent includes an acrylate polymer; The acrylate polymer comprises the structural unit shown in formula (Ⅰ). Equation (I); In formula (Ⅰ), R is an alkyl group having 2-20 carbon atoms; The acrylate polymer has a weight-average molecular weight of 350,000-450,000 g / mol and a number-average molecular weight of 250,000-350,000 g / mol; the median particle size D of the polymer emulsion plugging agent is... 50 The wavelength range is 80-520nm.
2. The polymer emulsion plugging agent according to claim 1, wherein, The molecular weight distribution of the acrylate polymer is 1.2-1.4; Preferably, the weight-average molecular weight of the acrylate polymer is 370,000-430,000 g / mol; Preferably, the number-average molecular weight of the acrylate polymer is 270,000-330,000 g / mol; Preferably, the median particle size D of the polymer emulsion plugging agent is... 50 The wavelength range is 100-300nm, more preferably 180-200nm; Preferably, the polymer emulsion plugging agent has a solid content of 15-25 wt%, more preferably 19-21 wt%.
3. The polymer emulsion plugging agent according to claim 1 or 2, wherein, In formula (Ⅰ), R is an alkyl group having 3-18 carbon atoms; Preferably, the acrylate polymer is obtained by emulsion polymerization of acrylate soft monomers; Preferably, the acrylate soft monomer is selected from at least one of butyl acrylate, isooctyl acrylate, and octadecyl acrylate.
4. The polymer emulsion plugging agent according to any one of claims 1-3, wherein, The polymer emulsion plugging agent also contains an emulsifier; Preferably, in the polymer emulsion plugging agent, the mass ratio of the acrylate polymer to the emulsifier is (170-180):(11-13), more preferably (170-180):(11.5-12.8). Preferably, the emulsifier comprises ionic emulsifiers and nonionic emulsifiers; Preferably, in the emulsifier, the mass ratio of the nonionic emulsifier to the ionic emulsifier is 3-5:1, more preferably 3.2-4:1; Preferably, the polymer emulsion plugging agent further contains a solvent, and the content of the acrylate polymer is 15-25 wt%.
5. A method for preparing a polymer emulsion plugging agent, characterized in that, The method includes carrying out an emulsion polymerization reaction of an emulsion system containing acrylate soft monomers and an emulsifier in the presence of an initiator and in a protective atmosphere. The emulsifier includes ionic emulsifiers and nonionic emulsifiers; The acrylate soft monomer has the structure shown in formula (II). Formula (II); In formula (II), R is an alkyl group having 2-20 carbon atoms; In the emulsifier, the mass ratio of the nonionic emulsifier to the ionic emulsifier is 3-5:
1.
6. The preparation method according to claim 5, wherein, The mass ratio of the acrylate soft monomer to the emulsifier is (170-180):(11-13), preferably (170-180):(11.5-12.8). Preferably, in formula (II), R is an alkyl group having 3-18 carbon atoms; Preferably, in the emulsion system, the acrylate monomers in the monomers undergoing emulsion polymerization contain a mass percentage of not less than 60 wt%, and more preferably not less than 90 wt%. Preferably, the acrylate soft monomer is selected from at least one of butyl acrylate, isooctyl acrylate, and octadecyl acrylate.
7. The preparation method according to claim 5 or 6, wherein, In the emulsifier, the mass ratio of the nonionic emulsifier to the ionic emulsifier is 3.2-4:1; Preferably, the nonionic emulsifier is an alkylphenol polyoxyethylene ether; Preferably, the ionic emulsifier is an alkyl sulfate, and more preferably selected from at least one of dodecyl sulfate, tridecyl sulfate, and tetradecyl sulfate.
8. The preparation method according to any one of claims 5-7, wherein, The initiator is added in the form of an initiator solution; Preferably, the initiator concentration in the initiator solution is 3-5% by mass; Preferably, the initiator is a persulfate, more preferably potassium persulfate and / or ammonium persulfate; Preferably, the mass ratio of the acrylate soft monomer to the initiator is (170-180):(1.3-1.5). Preferably, the initiator is added at a time of 15-30 minutes.
9. The preparation method according to any one of claims 5-8, wherein, The pH value of the emulsification system is 8-9; Preferably, the emulsion system further includes water as a solvent; Preferably, the mass ratio of the acrylate soft monomer to the solvent is (170-180):(700-750). Preferably, the preparation method of the emulsion system includes: mixing and emulsifying acrylate soft monomers, emulsifiers and solvents for 15-25 minutes; Preferably, the conditions for the emulsion polymerization reaction include: a polymerization temperature of 60-90℃, more preferably 70-80℃; and a polymerization time of 1-4h, more preferably 1.5-2.5h.
10. A polymer emulsion blocker prepared by any one of claims 5-9.
11. The application of the polymer emulsion plugging agent according to any one of claims 1-4 and 10 in the field of drilling fluids.
12. A drilling fluid, characterized in that, The drilling fluid comprises the polymer emulsion plugging agent and base fluid as described in any one of claims 1-4 and 10; Preferably, the base liquid is an oil-based base liquid and / or a biomass-based base liquid; Preferably, the drilling fluid further comprises a filtration loss reducer; Preferably, the drilling fluid further comprises a drilling fluid emulsifier; Preferably, in the drilling fluid, based on a volume of 100 mL of the base fluid, the content of the polymer emulsion plugging agent is 0.5-3 g, more preferably 1-2 g.
13. The drilling fluid according to claim 12, wherein, In the drilling fluid, based on a volume of 100 mL of the base fluid, the content of the filtration loss reducer is 3-5 g, preferably 3.5-4.5 g; Preferably, the filtration loss reducing agent is selected from at least one of core-shell structural materials, oxidized bitumen, and humic acid modified materials; Preferably, the core-shell structure material comprises a core and a shell covering the surface of the core; the core comprises an oxygen vacancy-type metal oxide and / or an oxygen vacancy-type doped transition metal oxide, and the shell is a polymer layer; Preferably, as characterized by XPS, the area of the hole oxygen peak in the core of the core-shell structured material accounts for no less than 18% of the total peak area, more preferably 24%-50%, and even more preferably 30%-50%. Preferably, the mass ratio of the shell to the core is 1:1-10, and more preferably 1:2-5.
14. The drilling fluid according to claim 13, wherein, The shell layer has a coverage rate of 60-100%, preferably 80-100%; Preferably, the average thickness of the shell layer is 2-28 nm, more preferably 8-22 nm; Preferably, the average particle size of the core is 50-2000 nm, more preferably 50-500 nm; Preferably, the oxygen-vacancy type metal oxide is a lanthanide rare earth metal oxide and / or a transition metal oxide, and is preferably selected from at least one of cerium oxide, lanthanum oxide, ferric oxide, vanadium pentoxide and manganese dioxide.
15. The drilling fluid according to claim 13 or 14, wherein, The oxygen vacancy-type doped transition metal oxide includes transition metal oxides and doped metal oxides; Preferably, based on metal elements, the molar ratio of doped metal to transition metal in the oxygen vacancy-type doped transition metal oxide is 1:0.5-6, more preferably 1:1-5; Preferably, the transition metal is selected from at least one of Fe, Co, and Ni; Preferably, the doped metal is selected from at least one of Ca, Mg, K, Ce and La.
16. The drilling fluid according to any one of claims 13-15, wherein, The average particle size of the core-shell structure material is 50-2000 nm, preferably 50-500 nm; Preferably, when the core is an oxygen vacancy type metal oxide, the polymer monomer of the shell layer includes a soft monomer and a hard monomer, wherein the soft monomer is butyl acrylate and / or methyl acrylate, and the hard monomer is selected from at least one of pyrrole, styrene and aniline; Preferably, when the core is an oxygen vacancy-doped transition metal oxide, the polymer monomers of the shell are polycarboxylic acids and polyols.
17. The drilling fluid according to any one of claims 13-16, wherein, The preparation method of the core-shell structure material includes the following steps: The core is brought into contact with the polymer monomer, and the polymer monomer undergoes in-situ chain growth on the core. The core comprises oxygen-vacancy type metal oxides and / or oxygen-vacancy type doped transition metal oxides. XPS characterization showed that the area of the hole oxygen peak in the core of the core-shell structured material accounted for no less than 18% of the total peak area; Preferably, the amount of the polymer monomer used is such that the average thickness of the shell layer is 2-28 nm; Preferably, the conditions for the in-situ chain growth reaction include: a reaction temperature of 15-90℃, more preferably 25-60℃; and a reaction pressure of 0.5-0.7MPa, more preferably 0.55-0.65MPa.
18. The drilling fluid according to any one of claims 13-17, wherein, The method for preparing oxygen vacancy-type doped transition metal oxides includes: contacting a transition metal source and a doped metal source with an excess polycarboxylic acid solution to carry out a precipitation reaction, separating the reaction product into solid and liquid components, and calcining the obtained solid product to obtain oxygen vacancy-type doped transition metal oxides. Preferably, the conditions for the precipitation reaction include: a reaction time of 10-30 min; and a reaction temperature of 0-8 °C. And / or, the calcination conditions include: a calcination temperature of 400-600℃; and a calcination time of 2-8h.
19. The drilling fluid according to any one of claims 12-18, wherein, Based on a base fluid volume of 100 mL, the drilling fluid emulsifier content is 2-7 g; Preferably, the drilling fluid emulsifier is a polyester amide ether and / or an emulsifier composition; Preferably, the emulsifier composition comprises a polyamine oligomer, a polyhydroxy oligomer, and a solvent; Preferably, based on the weight of the emulsifier composition, the content of the polyhydroxy oligomer is 40-50 wt%; the content of the polyamine oligomer is 30-40 wt%; and the content of the solvent is 10-30 wt%. Preferably, the particle size of the emulsifier composition is 5-6 μm.
20. The drilling fluid according to claim 19, wherein, The number-average molecular weight of the polyhydroxy oligomer is 1800-5000 g / mol; Preferably, the hydroxyl value of the polyhydroxy oligomer is 210-600 mg KOH / g; Preferably, the structural unit of the polyhydroxy oligomer contains at least one phenolic hydroxyl group, at least one amino group, and at least one alcoholic hydroxyl group.
21. The drilling fluid according to claim 19 or 20, wherein, The polyhydroxy oligomer comprises a structural unit A from an alkylphenol and a structural unit B from an alkanolamine, wherein two adjacent structural units A are connected by an alkylene group having 1-6 carbon atoms, and structural unit B is connected to the benzene ring of structural unit A by an alkylene group having 1-6 carbon atoms. Preferably, the polyhydroxy oligomer comprises structural units shown in Formula III and / or Formula IV, wherein the benzene rings between two adjacent structural units are connected by R5. Formula III; Formula IV; In Formulas III and IV, R1 is a saturated or unsaturated hydrocarbon group with 8-15 carbon atoms, R2 is an alkylene group with 1-3 carbon atoms, R3 is H, hydroxymethyl, hydroxyethyl, aminomethyl or aminoethyl, and R4 and R5 are each independently an alkylene group with 1-6 carbon atoms. Preferably, based on the weight of the polyhydroxy oligomer, the content of structural unit A from alkylphenol is 50-70 wt%; the content of alkylene with 1-6 carbon atoms is 10-20 wt%; and the content of structural unit B from alkanolamine is 10-40 wt%.
22. The drilling fluid according to any one of claims 19-21, wherein, The number-average molecular weight of the polyamine oligomer is 4000-10000 g / mol; Preferably, the amine value of the polyamine oligomer is 400-1000 mg KOH / g; Preferably, the structural unit of the polyamine oligomer contains at least one phenolic hydroxyl group and at least one amino group; Preferably, the polyamine oligomer comprises a structural unit A from an alkylphenol and a structural unit C from a polyamine; two adjacent structural units A are connected by an alkylene group having 1-6 carbon atoms, and the two ends of structural unit C are respectively connected to the benzene rings of the two structural units A by alkylene groups having 1-6 carbon atoms. Preferably, based on the weight of the polyamine oligomer, the content of structural unit A from alkylphenol is 50-60 wt%; the content of alkylene with 1-6 carbon atoms is 5-15 wt%; and the content of structural unit C from polyamine is 25-45 wt%.
23. The drilling fluid according to any one of claims 19-22, wherein, The method for preparing the polyhydroxy oligomer includes: (A) In the presence of an acidic catalyst, alkylphenol and a first aldehyde are brought into contact to carry out a first condensation reaction; (B) Contact the system after the reaction in step (A) with an alcohol amine and a second aldehyde to carry out a second condensation reaction; In step (A), the molar ratio of alkylphenol to alkanolamine in step (B) is 1:0.9-1.1; Preferably, the first aldehyde and the second aldehyde are each independently an aldehyde having 1-6 carbon atoms and its oligomers, preferably selected from at least one of paraformaldehyde, acetaldehyde, propionaldehyde and butyraldehyde; Preferably, the alkylphenol has the structure shown in Formula V. Formula V; In formula V, R1 is a saturated or unsaturated hydrocarbon group with 8-15 carbon atoms; Preferably, the alkylphenol is cashew phenol and / or urushiol.
24. The drilling fluid according to any one of claims 19-23, wherein, In step (A), the molar ratio of the alkylphenol to the first aldehyde is 1:0.5-0.8; And / or, in step (A), the first condensation reaction conditions include: a reaction temperature of 70-100°C; and a reaction time of 2-5 h. Preferably, the acidic catalyst is selected from at least one of hydrochloric acid, sulfuric acid, dodecylbenzenesulfonic acid, aminosulfonic acid, and oxalic acid; Preferably, the amount of acidic catalyst used is 0.5-1 wt% of the amount of alkylphenol used.
25. The drilling fluid according to any one of claims 19-24, wherein, In step (B), the molar ratio of the alkanolamine to the second aldehyde is 1:0.9-1.05; Preferably, the alkanolamine is selected from at least one of ethanolamine, diethanolamine, isopropanolamine, and hydroxyethyl ethylenediamine; Preferably, the molar ratio of alkylphenol in step (A) to alkanolamine in step (B) is 1:0.95-1.05; Preferably, in step (B), the conditions for the second condensation reaction include: a reaction temperature of 60-90°C and a reaction time of 1-4 hours.
26. The drilling fluid according to any one of claims 19-25, wherein, The method for preparing the polyamine oligomer includes: (a) In the presence of an amine catalyst, an alkylphenol is brought into contact with a third aldehyde to carry out a third condensation reaction; (b) Contact the system after the reaction in step (a) with a polyamine and a fourth aldehyde to carry out a fourth condensation reaction; Preferably, the amine catalyst is selected from at least one of triethylamine, diethylamine, and diisopropylethylamine; Preferably, the amount of the amine catalyst used is 0.5-1 wt% of the amount of alkylphenol used.
27. The drilling fluid according to any one of claims 19-26, wherein, In step (a), the molar ratio of the alkylphenol to the third aldehyde is 1:1-1.2; Preferably, in step (a), the conditions for the third condensation reaction include: a reaction temperature of 90-110°C and a reaction time of 2-5 hours; Preferably, in step (b), the molar ratio of the polyamine to the fourth aldehyde is 1:1.1-1.3; Preferably, the molar ratio of alkylphenol in step (a) to polyamine in step (b) is 1:0.9-1.1; Preferably, in step (b), the conditions for the fourth condensation reaction include: a reaction time of 70-100°C and a reaction time of 1-4 hours.
Citation Information
Patent Citations
Preparation method of while-drilling plugging fluid for oil-based drilling fluid
CN104448136A
Biomass alcohol ether and preparation method thereof, and drilling fluid
CN107304160A
A biomass base oil and its preparation method
CN110699051B
Emulsifier for biomass synthetic drilling fluid, preparation method thereof and biomass synthetic drilling fluid
CN114685305B
Humic acid filtrate reducer as well as preparation method and application thereof
CN115403785A
